Adhesive layer-forming composition, laminate, method for manufacturing laminate, and method for processing laminate
Patent Information
- Application Number
- JP2024120309
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-14
AI Technical Summary
【0026】 本発明によれば、高いアルカリ耐性を有し、レーザー加工性も有する接着剤層形成用組成物、前記接着剤層形成用組成物を用いて支持体と被着体とを接着してなる積層体、前記積層体の製造方法及び処理方法、ならびにパターニングされたマテリアル層を含む積層体の製造方法を提供される。
Smart Images

Figure 2025036146000001 
Figure 2025036146000002 
Figure 2025036146000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for forming an adhesive layer, a laminate, and a method for producing and treating a laminate. [Background technology]
[0002] In recent years, as digital devices and other devices have become more functional, the flexible displays and semiconductor chips they are equipped with have become thinner. However, as these devices have become thinner, their strength has decreased, making it difficult to transport them using conventional automatic transport methods.
[0003] In view of this, methods have been considered for easily transporting thin flexible displays, semiconductor chips, etc. For example, in this method, a laminate having an adherend such as a semiconductor wafer fixed on a support such as a glass substrate via an adhesive layer is irradiated with light from the support side toward the adhesive layer, thereby altering or decomposing the adhesive layer and reducing the adhesive force, thereby separating the support and the adherend.
[0004] Patent Document 1 also describes a method for separating the support from the supported substrate, in a laminate having a support, a supported substrate, an adhesive layer disposed on the surface of the supported substrate that is supported by the support, and a separation layer disposed between the support substrate and the supported substrate, by irradiating the separation layer with light to alter the polymer contained in the separation layer. Patent Document 1 states that the separation layer is altered by irradiation with light and loses its adhesiveness, so that the support substrate and the supported substrate can be easily separated. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-106486 A Summary of the Invention [Problem to be solved by the invention]
[0006] 2. Description of the Related Art When forming a pattern of a metal film or the like on a substrate such as a semiconductor wafer, a pattern processing technique using a resist material is generally used.
[0007] For example, when an etching process is used, a pattern of a metal film or the like may be formed on a substrate through the following steps: a) a preparation step of providing a material layer such as a metal film on a substrate and then forming a resist layer on the material layer, b) an exposure step of irradiating a part of the resist layer with radiation through a photomask, c) a development step of developing the resist layer irradiated with radiation and removing the unexposed part, d) a patterning step of removing the material layer by etching from the part where the resist layer has been removed, and e) a stripping step of stripping the resist layer with an alkaline stripping solution. The alkaline stripping solution used in the above process is a strong alkaline solution in order to remove the resist material, and the process is often carried out under relatively high temperature conditions.
[0008] In this case, in order to improve the transport stability of the substrate, a laminate having an adherend such as a semiconductor wafer fixed on a support such as a glass substrate via an adhesive layer can be used as the substrate, but the adhesive layer used for such an application is required to have high alkali resistance. In addition, there are cases where the adhesive layer is required to have high alkali resistance, and an adhesive layer having high alkali resistance has been needed.
[0009] However, according to the findings of the present inventors, when the laminate described in Patent Document 1 was used to perform pattern processing using a resist material, there was a problem in that the adhesive strength of the adhesive layer was reduced when the resist layer was peeled off with an alkaline stripping solution.
[0010] The present invention has been made in consideration of these points, and aims to provide a composition for forming an adhesive layer that has high alkali resistance and also has laser processability, a laminate obtained by adhering a support and an adherend using the composition for forming an adhesive layer, a manufacturing method and processing method for the laminate, and a manufacturing method for a laminate including a patterned material layer. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors conducted extensive research and found that a composition for forming an adhesive layer containing an unsaturated group-containing alkali-soluble resin and further containing a relatively large amount of an epoxy compound having two or more epoxy groups relative to a saturated group-containing alkali-soluble resin is suitable as an adhesive layer, and thus completed the present invention.
[0012] The reason for this is not necessarily clear, but is thought to be as follows. In the process of bonding the support and the adherend via the adhesive layer, the laminate is heat-treated to dry the solvent. At this time, thermal crosslinking between the unsaturated groups of the unsaturated group-containing alkali-soluble resin proceeds. Furthermore, thermal crosslinking between the acidic groups for expressing alkali solubility of the unsaturated group-containing alkali-soluble resin and the epoxy groups of the epoxy compound also proceeds. This allows a strong crosslinked structure to be formed, and since the composition contains a relatively large amount of epoxy compound, the acidic groups for expressing alkali solubility are significantly consumed by the crosslinking reaction, thereby improving alkali resistance. In addition, this unsaturated group-containing alkali-soluble resin absorbs lasers well, so it generates heat when irradiated with a laser. This causes the unsaturated group-containing alkali-soluble resin to change in quality, allowing the adherend to be peeled off, thereby improving laser processability.
[0013] That is, the above problem can be solved by the following configuration.
[0014] [1] A laminate having an adhesive layer between a light-transmitting support and an adherend, A composition for forming an adhesive layer, which enables the support and the adherend to be separated from the laminate by irradiating light from the support side, The adhesive layer-forming composition is (A) an unsaturated group-containing alkali-soluble resin; (B) an epoxy compound having at least two epoxy groups; (D) a solvent; Including, The content of the (B) epoxy compound is 25% by mass to 70% by mass based on the total mass of the (A) unsaturated group-containing alkali-soluble resin. Composition for forming adhesive layer.
[0015] [2] The epoxy compound (B) has an aromatic ring and / or an alicyclic structure. The adhesive layer forming composition according to [1].
[0016] [3] The epoxy compound (B) is The absorbance of a 0.001% by weight acetonitrile solution is measured using an ultraviolet, visible, and infrared spectrophotometer in a quartz cell with an optical path length of 1 cm, and the absorbance of light at a wavelength of 266 nm is 0.10 or more. The adhesive layer forming composition according to [1] or [2].
[0017] [4] The (A) unsaturated group-containing alkali-soluble resin is The weight average molecular weight is 1,000 to 40,000. The acid value is 20mgKOH / g~200mgKOH / g. The adhesive layer-forming composition according to any one of [1] to [3].
[0018] [5] (C) a polymerizable compound having at least one ethylenically unsaturated bond, The content of the (C) polymerizable compound is 1 mass % to 10 mass % based on the total mass of the (A) unsaturated group-containing alkali-soluble resin and the (B) epoxy compound. The composition for forming an adhesive layer according to any one of [1] to [4].
[0019] [6] A support; An adherend; an adhesive layer including a coating film or a cured film of the adhesive layer-forming composition according to any one of [1] to [5], which is disposed between the support and the adherend; A laminate having the following structure:
[0020] [7] A resist layer is provided on the surface of the adherend opposite to the surface on which the adhesive layer is provided, The resist layer is disposed in contact with an adherend, or disposed so as to sandwich a material layer between the resist layer and the adherend. The laminate according to [6].
[0021] [8] The adherend includes a patterned material layer disposed on a surface opposite to the surface on which the adhesive layer is disposed. The laminate according to [6].
[0022] [9] A step of forming an adhesive layer on one or both of a support and an adherend using the adhesive layer-forming composition according to any one of [1] to [5]; a step of adhering the support and the adherend via the formed adhesive layer; A method for producing a laminate comprising the steps of:
[0023]
[10] A step of applying a resist layer to the adherend, The resist layer is disposed on a surface opposite to a surface on which the adhesive layer is disposed. A method for producing the laminate described in [9].
[0024]
[11] A step of preparing a laminate according to any one of [6] to [8]; preparing a laminate according to the present invention; A step of irradiating the adhesive layer with light to separate the support and the adherend; A method for treating a laminate, comprising: The support transmits light having a wavelength of 10 nm to 400 nm. Methods for processing laminates.
[0025]
[12] A support; An adherend; an adhesive layer including a coating film or a cured film of the adhesive layer-forming composition according to any one of [1] to [5], which is disposed between the support and the adherend; an unexposed resist layer disposed on a surface of the adherend opposite to a surface on which the adhesive layer is disposed; providing a laminate having an exposure step of irradiating a portion of the resist layer with radiation through a photomask; a developing step of developing the resist layer irradiated with radiation and removing the resist layer in exposed or unexposed areas; a stripping step of stripping the resist layer with an alkaline stripping solution; A method for producing a laminate including a patterned material layer, comprising: Effect of the Invention
[0026] According to the present invention, there are provided a composition for forming an adhesive layer which has high alkali resistance and also has laser processability, a laminate obtained by adhering a support and an adherend using the composition for forming an adhesive layer, a manufacturing method and processing method for the laminate, and a manufacturing method for a laminate including a patterned material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. In addition, in the present invention, when the first decimal place of the content of each component is 0, the notation after the decimal point may be omitted.
[0028] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0029] 1. Composition for forming adhesive layer The adhesive layer-forming composition according to this embodiment is (A) an unsaturated group-containing alkali-soluble resin (hereinafter also referred to simply as “component (A)”), (B) an epoxy compound having at least two epoxy groups (hereinafter also referred to simply as “component (B)”), (D) a solvent (hereinafter also referred to simply as "component (D)"); The content of the (B) epoxy compound is 25% by mass to 70% by mass based on the total mass of the (A) unsaturated group-containing alkali-soluble resin.
[0030] 1-1.(A) Alkali-soluble resin containing unsaturated groups The (A) component has a polymerizable unsaturated group and an acidic group for expressing alkali solubility. Any resin of this type can be used without any particular limitation. The polymerizable unsaturated groups react with each other, and the acidic groups react with the epoxy groups of the (B) component to form a strong crosslinked structure, and the acidic groups for expressing alkali solubility are consumed, thereby improving alkali resistance.
[0031] The polymerizable unsaturated group of component (A) is not particularly limited as long as it is a functional group having an unsaturated bond, but is preferably a (meth)acryloyl group, which can enhance curability and impart good alkali resistance.
[0032] In addition, the term "(meth)acryloyl group" is a general term for an acryloyl group and a methacryloyl group, "(meth)acrylic acid" is a general term for an acrylic acid and a methacrylic acid, and "(meth)acrylate" is a general term for an acrylate and a methacrylate, and each refers to one or both of these.
[0033] Examples of the acidic group that is possessed by the component (A) for imparting alkali solubility include a carboxy group, a phosphate group, and a sulfonic acid group, and the like. The carboxy group is preferred in that it can enhance the reactivity with the component (B).
[0034] It is preferable that the component (A) absorbs light well. When the component (A) absorbs the laser well and generates heat, the component (A) changes or decomposes, and the adherend can be peeled off well. The light to be absorbed is preferably ultraviolet light, more preferably light with a wavelength of 10 nm to 400 nm, even more preferably light with a wavelength of 100 nm to 400 nm, and most preferably light with a wavelength of 200 nm to 400 nm.
[0035] From the viewpoint of good light absorption, the (A) component preferably has a maximum absorbance of 0.10 or more, more preferably 0.10 to 1.50, and even more preferably 0.15 to 1.30, for light having a wavelength of 260 nm to 400 nm. When the absorbance is 0.10 or more, the adhesive layer can easily absorb ultraviolet light, and the alteration or decomposition of the cured film caused by laser irradiation can be more effectively promoted. When the absorbance is 1.50 or less, the exposure sensitivity is maintained, making patterning possible. The absorbance can be measured using a UV-Vis-Infrared Spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation) by measuring the absorbance of a 0.001 wt% propylene glycol monomethyl ether acetate (hereinafter also referred to as "PGMEA") solution in a quartz cell with an optical path length of 1 cm.
[0036] The acid value of component (A) is preferably 20 mgKOH / g to 200 mgKOH / g, and more preferably 30 mgKOH / g to 150 mgKOH / g. When the acid value is 50 mgKOH / g or more, residues are less likely to remain during alkaline development, and when the acid value is 200 mgKOH / g or less, the penetration of the alkaline developer is not too fast, so peeling development can be suppressed. The acid value can be determined by titration with a 1 / 10N-KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).
[0037] The weight average molecular weight (Mw) of the component (A) in terms of polystyrene as measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by Tosoh Corporation) is usually preferably 1000 to 100000, more preferably 1500 to 30000, and even more preferably 2000 to 15000. When the weight average molecular weight (Mw) is 1000 or more, the adhesion between the support and the adherend can be improved. When the weight average molecular weight (Mw) is less than 100000, the solution viscosity of the photosensitive resin composition is easily adjusted to a suitable level for application, and application to the surface of the support or adherend does not take too long.
[0038] Exemplary compounds of the component (A) that are preferably used in the composition for forming an adhesive layer of this embodiment are listed below, but are not limited to the following compounds.
[0039] 1-1-1. Example compound 1 of component (A) The component (A) is preferably an alkali-soluble resin containing a polymerizable unsaturated group obtained by further reacting a reaction product of an epoxy compound having two or more epoxy groups with (meth)acrylic acid with a polybasic carboxylic acid or an anhydride thereof. During the production of the alkali-soluble resin, a polyester is generated by the reaction of a hydroxyl group with a polybasic carboxylic acid, and the average degree of polymerization is preferably a low molecular weight of about 2 to 500.
[0040] The epoxy compound is preferably an epoxy compound having two or more epoxy groups. Examples of such epoxy compounds include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds (e.g., EPPN-501H: manufactured by Nippon Kayaku Co., Ltd.), phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy compounds (e.g., jER YX4000: manufactured by Mitsubishi Chemical Corporation), naphthol aralkyl type epoxy compounds, trisphenol methane type epoxy compounds, tetrakisphenol ethane type epoxy compounds, glycidyl ethers of polyhydric alcohols, glycidyl esters of polycarboxylic acids, copolymers of monomers having (meth)acrylic groups containing glycidyl (meth)acrylate as a unit, such as copolymers of methacrylic acid and glycidyl methacrylate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate (e.g., Celloxide 2021P: manufactured by Daicel Corporation), butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε-caprolactone (for example, Epolead GT401: manufactured by Daicel Corporation), epoxy compounds having an epoxycyclohexyl group such as HiREM-1 manufactured by Shikoku Chemical Industry Co., Ltd., polyfunctional epoxy compounds having a dicyclopentadiene skeleton (for example, HP7200 series: manufactured by DIC Corporation), 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (for example, EHPE3150: manufactured by Daicel Corporation), epoxidized polybutadiene (for example, NISSO-PB·JP-100: manufactured by Nippon Soda Co., Ltd.), and epoxy compounds having a silicone skeleton.
[0041] From the viewpoint of further improving the alkali resistance of the cured film, it is preferable that the (A) component has at least one aromatic ring and alicyclic structure in the molecule. By making it have such a structure, even if the same amount is added, the alkali resistance is likely to be improved. It is more preferable that the (A) component has a plurality of aromatic rings, and it is even more preferable that it is an alkali-soluble resin having a repeating unit containing a fluorene structure, and it is even more preferable that it is an alkali-soluble resin having a repeating unit containing a bisarylfluorene skeleton. For example, the (A) component having a repeating unit containing a bisarylfluorene skeleton is preferably a resin represented by the following general formula (1).
[0042] [ka]
[0043] In formula (1), Ar are each independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted with a substituent selected from the group consisting of an alkyl group having 1 to 10 carbon atoms, an aryl group or arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group. R1 are each independently an alkylene group having 2 to 4 carbon atoms, and 1 are each independently a number from 0 to 3. G are each independently a (meth)acryloyl group or a substituent represented by the following general formula (2) or the following general formula (3), and Y is a tetravalent carboxylic acid residue. Z are each independently a hydrogen atom or a substituent represented by the following general formula (4), and at least one of them is a substituent represented by the following general formula (4). n is a number having an average value of 1 to 20.
[0044] [ka]
[0045] [ka]
[0046] In formulas (2) and (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0047] [ka]
[0048] In formula (4), W is a divalent or trivalent carboxylic acid residue, and m is the number 1 or 2. * indicates a bonding site.
[0049] In addition, Y in the above general formula (1) preferably contains at least one aromatic hydrocarbon group. Examples of aromatic hydrocarbon groups include a phenyl group, a biphenyl group, a benzophenone group, a naphthalene group, and a biphenyl ether group. Among the aromatic hydrocarbon groups, a biphenyl group, a benzophenone group, or a naphthalene group is preferable. When Y is an aromatic hydrocarbon group, the absorbance of the resin at a wavelength of 260 nm to 400 nm can be improved, and the alteration or decomposition of the cured film caused by the laser irradiation can be more effectively promoted.
[0050] Next, a method for producing the unsaturated group-containing alkali-soluble resin (A) represented by the above general formula (1) will be described in detail.
[0051] First, an epoxy compound (a-1) having a bisarylfluorene skeleton represented by the following general formula (5) (hereinafter simply referred to as "epoxy compound (a-1)"), which may have several oxyalkylene groups in one molecule, is reacted with either or both of (meth)acrylic acid and a (meth)acrylic acid derivative represented by the following general formula (6) or the following general formula (7) to obtain a diol compound which is an epoxy (meth)acrylate. The bisarylfluorene skeleton is preferably a bisnaphtholfluorene skeleton or a bisphenolfluorene skeleton.
[0052] [ka]
[0053] In formula (5), Ar are each independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted with an alkyl group having 1 to 10 carbon atoms, an aryl group or arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. R1 are each independently an alkylene group having 2 to 4 carbon atoms, and 1 are each independently a number from 0 to 3.
[0054] [ka]
[0055] [ka]
[0056] In formulas (6) and (7), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10.
[0057] The reaction of the epoxy compound (a-1) with the (meth)acrylic acid or (meth)acrylic acid derivative can be carried out by a known method. For example, JP-A-4-355450 describes that a diol compound containing a polymerizable unsaturated group can be obtained by using about 2 moles of (meth)acrylic acid per mole of an epoxy compound having two epoxy groups. In this embodiment, the compound obtained by the reaction is a diol (d) containing a polymerizable unsaturated group represented by formula (8) (hereinafter, also simply referred to as "diol (d) represented by general formula (8)").
[0058] [ka]
[0059] In formula (8), Ar are each independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted with an alkyl group having 1 to 10 carbon atoms, an aryl group or arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. G are each independently a (meth)acryloyl group or a substituent represented by the following general formula (2) or general formula (3), R1 are each independently an alkylene group having 2 to 4 carbon atoms, and 1 are each independently a number from 0 to 3.
[0060] [ka]
[0061] [ka]
[0062] In formulas (2) and (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0063] In the synthesis of the diol (d) represented by the general formula (8) and the subsequent production of the unsaturated group-containing alkali-soluble resin represented by the general formula (1) by reacting the diol with a polycarboxylic acid or an anhydride thereof, the reaction is usually carried out in a solvent using a catalyst as necessary.
[0064] Examples of the solvent include cellosolve-based solvents such as ethyl cellosolve acetate and butyl cellosolve acetate, high-boiling ether or ester-based solvents such as diglyme, ethyl carbitol acetate, butyl carbitol acetate, and propylene glycol monomethyl ether acetate, and ketone-based solvents such as cyclohexanone and diisobutyl ketone. There are no particular limitations on the reaction conditions such as the solvent and catalyst used, but it is preferable to use, for example, a solvent that does not have a hydroxyl group and has a boiling point higher than the reaction temperature as the reaction solvent.
[0065] In addition, it is preferable to use a catalyst in the reaction between an epoxy group and a carboxy group or a hydroxyl group. JP-A-9-325494 describes ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, and phosphines such as triphenylphosphine and tris(2,6-dimethoxyphenyl)phosphine.
[0066] Next, the diol (d) represented by the general formula (8) obtained by the reaction of the epoxy compound (a-1) with the (meth)acrylic acid derivative is reacted with a dicarboxylic acid or tricarboxylic acid or anhydride thereof (b), and a tetracarboxylic acid or anhydride thereof (c) to obtain an alkali-soluble resin having a carboxy group and a polymerizable unsaturated group in one molecule represented by the following general formula (1).
[0067] [ka]
[0068] In formula (1), Ar are each independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted with an alkyl group having 1 to 10 carbon atoms, an aryl group or arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. R1 are each independently an alkylene group having 2 to 4 carbon atoms, and 1 are each independently a number from 0 to 3. G are each independently a (meth)acryloyl group or a substituent represented by the following general formula (2) or the following general formula (3), and Y is a tetravalent carboxylic acid residue. Z are each independently a hydrogen atom or a substituent represented by the following general formula (4), and at least one of them is a substituent represented by the following general formula (4). n is a number having an average value of 1 to 20.
[0069] [ka]
[0070] [ka]
[0071] In formulas (2) and (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0072] [ka]
[0073] In formula (4), W is a divalent or trivalent carboxylic acid residue, and m is 1 or 2. * indicates a bonding site.
[0074] The acid component used to synthesize the unsaturated group-containing alkali-soluble resin represented by general formula (1) is a polyvalent acid component capable of reacting with the hydroxyl group in the diol (d) molecule represented by general formula (8), and it is preferable to use a dicarboxylic acid or tricarboxylic acid or an acid monoanhydride thereof (b) in combination with a tetracarboxylic acid or an acid dianhydride thereof (c). The carboxylic acid residue of the acid component may be either a saturated or unsaturated hydrocarbon group. In addition, these carboxylic acid residues may contain bonds containing heteroatoms such as -O-, -S-, and carbonyl groups.
[0075] Examples of the dicarboxylic acid or tricarboxylic acid or the acid monoanhydride thereof (b) include chain hydrocarbon dicarboxylic acid or tricarboxylic acid, alicyclic hydrocarbon dicarboxylic acid or tricarboxylic acid, aromatic hydrocarbon dicarboxylic acid or tricarboxylic acid, or the acid monoanhydride thereof, and the like.
[0076] Examples of the acid monoanhydrides of the above-mentioned chain hydrocarbon dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, diglycolic acid, and the like, and acid monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent has been introduced.
[0077] Examples of the acid monoanhydrides of the alicyclic hydrocarbon dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of cyclobutanedicarboxylic acid, cyclopentanedicarboxylic acid, hexahydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, norbornanedicarboxylic acid, and the like, as well as acid monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent has been introduced.
[0078] Examples of the acid monoanhydrides of the aromatic hydrocarbon dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of phthalic acid, isophthalic acid, trimellitic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, and the like, and acid monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent has been introduced.
[0079] Among the above dicarboxylic acid or tricarboxylic acid monoanhydrides, succinic acid, itaconic acid, 1,2,3,6-tetrahydrophthalic acid, hexahydrotrimellitic acid, phthalic acid, trimellitic acid, 1,8-naphthalenedicarboxylic acid, and 2,3-naphthalenedicarboxylic acid are preferred, and 1,2,3,6-tetrahydrophthalic acid, 1,8-naphthalenedicarboxylic acid, and 2,3-naphthalenedicarboxylic acid are more preferred.
[0080] In addition, in the case of dicarboxylic acids or tricarboxylic acids, it is preferable to use their acid monoanhydrides. The above-mentioned acid monoanhydrides of dicarboxylic acids or tricarboxylic acids may be used alone or in combination of two or more kinds.
[0081] Examples of the tetracarboxylic acid or its dianhydride (c) include chain hydrocarbon tetracarboxylic acid, alicyclic hydrocarbon tetracarboxylic acid, aromatic hydrocarbon tetracarboxylic acid, or their dianhydrides.
[0082] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and chain hydrocarbon tetracarboxylic acids having a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group introduced therein.
[0083] Examples of the alicyclic hydrocarbon tetracarboxylic acid include cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, and alicyclic tetracarboxylic acids having a substituent such as a chain hydrocarbon group or an unsaturated hydrocarbon group introduced therein.
[0084] Examples of aromatic hydrocarbon tetracarboxylic acids include pyromellitic acid, benzophenone tetracarboxylic acid, 3,3',4,4'-biphenyl tetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid.
[0085] In addition, bis(trimellitic anhydride) aryl esters can also be used. Bis(trimellitic anhydride) aryl esters are a group of compounds produced, for example, by the method described in International Publication No. 2010 / 074065, and are structurally dianhydrides in which two hydroxyl groups of an aromatic diol (such as naphthalenediol, biphenol, terphenyldiol, etc.) react with the carboxyl groups of two molecules of trimellitic anhydride to form an ester bond. Hereinafter, these compounds will be referred to as bis(trimellitic anhydride) esters of aromatic diols.
[0086] Among the above tetracarboxylic acids or their dianhydrides, 3,3',4,4'-biphenyltetracarboxylic acid, benzophenonetetracarboxylic acid, diphenylethertetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid are preferred, and 3,3',4,4'-biphenyltetracarboxylic acid, benzophenonetetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid are more preferred. In addition, in the above tetracarboxylic acids or their dianhydrides, it is preferred to use the dianhydrides. Furthermore, bis(trimellitic anhydride) esters of naphthalenediol can also be preferably used. The above tetracarboxylic acids or their dianhydrides, and bis(trimellitic anhydride) esters of aromatic diols may be used alone or in combination of two or more.
[0087] The reaction of the diol (d) represented by the general formula (8) with the acid components (b) and (c) is not particularly limited, and any known method can be used. For example, JP-A-9-325494 describes a method in which an epoxy (meth)acrylate is reacted with a tetracarboxylic dianhydride at a reaction temperature of 90 to 140° C.
[0088] Here, it is preferable to react the compound so that the terminals of the compound become carboxy groups, and the molar ratio of the compound with the epoxy (meth)acrylate (d), dicarboxylic acid or tricarboxylic acid or their monoanhydrides (b), and tetracarboxylic dianhydride (c) is (d):(b):(c)=1.0:0.01-1.0:0.2-1.0.
[0089] For example, when an acid monoanhydride (b) and an acid dianhydride (c) are used, it is preferable to react them so that the molar ratio [[(b) / 2+(c)] / (d)] of the diol (d) containing a polymerizable unsaturated group to the amount of the acid component [(b) / 2+(c)] is 0.5 to 1.0. Here, when the molar ratio is 0.5 or more, the content of the diol containing an unreacted polymerizable unsaturated group is not increased, so the stability over time of the alkali-soluble resin composition can be improved. On the other hand, when the molar ratio is 1.0 or less, the terminal of the alkali-soluble resin represented by the general formula (1) does not become an acid anhydride, so that the content of the unreacted acid dianhydride can be suppressed from increasing, so the stability over time of the alkali-soluble resin composition can be improved. In addition, in order to adjust the acid value and molecular weight of the alkali-soluble resin represented by the general formula (1), the molar ratios of each component (b), (c) and (d) can be arbitrarily changed within the above-mentioned range.
[0090] In the adhesive layer-forming composition of the present embodiment, the content of the unsaturated group-containing alkali-soluble resin (A) represented by the above general formula (1) is preferably 10% by mass to 80% by mass, more preferably 30% by mass to 80% by mass, and even more preferably 50% by mass to 80% by mass, based on the total mass of the solid content. If the content of the above component (A) is 10% by mass or more based on the total mass of the solid content, it is likely to absorb irradiated light (e.g., ultraviolet light) and change in quality, so that the support and the adherend can be easily separated. If the content is 80% by mass or less, the acidic groups for expressing alkali solubility can be sufficiently consumed by the crosslinking reaction with the component (B), so that the alkali resistance can be improved.
[0091] The acid value of the unsaturated group-containing alkali-soluble resin (A) represented by general formula (1) is preferably 20 mgKOH / g to 200 mgKOH / g, more preferably 30 mgKOH / g to 150 mgKOH / g. When the acid value is 20 mgKOH / g or more, residues are less likely to remain during alkaline development, and when the acid value is 200 mgKOH / g or less, the penetration of the alkaline developer is not too fast, so peeling development can be suppressed. The acid value can be determined by titration with a 1 / 10N-KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).
[0092] The weight average molecular weight (Mw) of the unsaturated group-containing alkali-soluble resin (A) represented by the general formula (1) is preferably 1000 to 100000, more preferably 1500 to 30000, and even more preferably 2000 to 15000, in terms of polystyrene, as measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by Tosoh Corporation). When the weight average molecular weight (Mw) is 1000 or more, the adhesion between the support and the adherend can be improved. When the weight average molecular weight (Mw) is less than 100000, the solution viscosity of the photosensitive resin composition is easily adjusted to a level suitable for application, and application to the surface of the support or adherend does not take too much time.
[0093] 1-1-2. Example compound 2 of component (A) As the component (A), a (meth)acrylic copolymer is also preferably used.
[0094] The component (A) may be, for example, a (meth)acrylic copolymer formed by combining any or all of the following structural units (AA) to (AE) derived from different monomers. The (meth)acrylic copolymer contains the structural unit (AB) and the structural unit (AC) or contains the structural unit (AD). (AA) Structural unit having an ultraviolet absorbing group (AB) a structural unit having a polymerizable unsaturated group and no carboxy group (AC) a structural unit having a carboxy group and no polymerizable unsaturated group (AD) Structural unit having a polymerizable unsaturated group and a carboxy group (AE) a structural unit having no ultraviolet absorbing group, no polymerizable unsaturated group, and no carboxy group
[0095] The structural unit (AA) is a structural unit having an ultraviolet absorbing group, and the (meth)acrylic copolymer preferably contains the structural unit (AA). By containing the structural unit (AA), light can be absorbed well and laser peelability can be improved. The structural unit (AA) may have the ultraviolet absorbing group in the main chain or in the side chain of the (meth)acrylic copolymer, but from the viewpoint of ease of production of the (meth)acrylic copolymer, it is preferable that the structural unit (AA) has the ultraviolet absorbing group in the side chain.
[0096] From the viewpoint of enhancing the ultraviolet absorbing ability of the (meth)acrylic copolymer, the structural unit (AA) is preferably a structural unit derived from a monomer having a molar absorption coefficient of 3000 L / (mol·cm) or more at a wavelength of 355 nm. From the same viewpoint, the structural unit (AA) is more preferably a structural unit derived from a monomer having a molar absorption coefficient of 3000 L / (mol·cm) to 100000 L / (mol·cm) at a wavelength of 355 nm, further preferably a structural unit derived from a monomer having a molar absorption coefficient of 4000 L / (mol·cm) to 90000 L / (mol·cm), and particularly preferably a structural unit derived from a monomer having a molar absorption coefficient of 5000 L / (mol·cm) to 80000 L / (mol·cm). The molar absorption coefficient can be calculated by measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation), and then dividing the measured value by the molar concentration.
[0097] The ultraviolet absorbing group includes functional groups having a benzotriazole structure, a benzophenone structure in which a portion of the hydrogen atoms contained in the benzene ring is substituted with a hydroxyl group (hereinafter, also simply referred to as a "substituted benzophenone structure"). A triazine structure, a salicylic acid structure, a benzoate structure, a cinnamic acid derivative structure, a diphenyl sulfoxide structure, a diphenyl sulfone structure, a diphenyl structure, a diphenylamine structure, a naphthalene derivative structure, a structure based on anthracene and its derivatives, a structure having a dinaphthalene structure, and a structure having a phenanthroline structure. Among these, functional groups having a benzotriazole structure, a substituted benzophenone structure, or a triazine structure are preferred, as they efficiently absorb 355 nm ultraviolet light, functional groups having a benzotriazole structure or a triazine structure are more preferred, and functional groups having a benzotriazole structure (hydroxyphenylbenzotriazole structure) are more preferred.
[0098] Examples of functional groups having a benzotriazole structure include 2-(2'-hydroxy-phenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole. These functional groups include those containing structures derived from compounds such as azole, 2-(2'-hydroxy-3',5'-di-t-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-{2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl}benzotriazole, and C7-C9-alkyl-3-[3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]propionether.
[0099] Examples of the functional group having a substituted benzophenone structure include functional groups containing a structure derived from a compound such as 4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone trihydrate, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, sodium 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfobenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 5-chloro-2-hydroxybenzophenone, and hydroxydodecylbenzophenone.
[0100] Examples of the functional group having a triazine structure include functional groups containing a structure derived from compounds such as 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-isooctyloxyphenyl)-1,3,5-triazine, 2-[4((2-hydroxy-3-dodecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-((2-hydroxy-3-tridecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.
[0101] The structural unit (AA) preferably does not have a polymerizable unsaturated group, and preferably does not have a carboxy group.
[0102] The structural unit (AB) is a structural unit having a polymerizable unsaturated group. However, in this specification, a structural unit having both a polymerizable unsaturated group and a carboxy group is a structural unit (AD) and is not included in the structural unit (AB).
[0103] Examples of the polymerizable unsaturated group include a vinyl group, an allyl group, and a (meth)acryloyl group, etc. Among these, a (meth)acryloyl group is preferred.
[0104] The polymerizable unsaturated group is preferably grafted to the side chain of the structural unit (AB). In other words, the polymerizable unsaturated group is preferably bonded to the side chain of the structural unit (AB) via a linking group or linking structure generated during grafting. Examples of the linking group or linking structure include an ester bond, a urethane bond, and an epoxy acrylate residue. Among these, the polymerizable unsaturated group is preferably grafted to the side chain via a urethane bond or an epoxy acrylate residue, because grafting is easy. From the viewpoint of further increasing the compatibility of the (meth)acrylic copolymer with other alkali-soluble resins (e.g., alkali-soluble resins having a fluorene skeleton), the polymerizable unsaturated group is preferably grafted to the side chain via a urethane bond, and from the viewpoint of making it easier to adjust the development speed, the polymerizable unsaturated group is preferably grafted to the side chain via an epoxy acrylate residue.
[0105] It is preferable that the structural unit (AB) does not have an ultraviolet absorbing group.
[0106] The structural unit (AC) is a structural unit having a carboxy group. However, in this specification, a structural unit having both a carboxy group and a polymerizable unsaturated group is a structural unit (AD) and is not included in the structural unit (AC).
[0107] The carboxy group may be a functional group derived from a monomer (e.g., (meth)acrylic acid, etc.) that is a material of the structural unit (AC), or may be grafted to a side chain in the structural unit (AC). In other words, the carboxy group may be bonded to a side chain in the structural unit (AC) via a linking group or linking structure generated during grafting. From the viewpoint of making it easier to adjust the development rate, it is preferable that the carboxy group is grafted to a side chain in the structural unit (AC). Examples of the linking group or linking structure include an ester bond, a urethane bond, and an epoxy acrylate residue. Among these, from the viewpoint of facilitating grafting, it is preferable that the carboxy group is grafted to a side chain via a urethane bond or an epoxy acrylate residue, and from the viewpoint of increasing the development rate, it is preferable that the carboxy group is grafted to a side chain via an ester bond.
[0108] It is preferable that the structural unit (AC) does not have an ultraviolet absorbing group.
[0109] The structural unit (AD) is a structural unit having a polymerizable unsaturated group and a carboxy group. The polymerizable unsaturated group is the functional group described for the structural unit (AB).
[0110] The polymerizable unsaturated group and the carboxyl group are preferably both grafted to the side chain of the structural unit (AD). In other words, the polymerizable unsaturated group is preferably bonded to the side chain of the structural unit (AD) via a linking group or linking structure generated during grafting. Examples of the linking group or linking structure include an ester bond, a urethane bond, and an epoxy acrylate residue. For example, after forming the skeleton of the structural unit (AD) by copolymerization of a monomer having a glycidyl group or an alicyclic epoxy group, a monomer having a polymerizable unsaturated group and a carboxyl group is reacted to form an epoxy acrylate to graft the polymerizable unsaturated group. Furthermore, the structural unit (AD) can be formed by reacting a polyvalent carboxylic acid or an anhydride thereof with the hydroxyl group generated by the formation of the epoxy acrylate to graft a carboxyl group. In the structural unit (AD) thus formed, the polymerizable unsaturated group and the carboxyl group are grafted to the side chain via an epoxy acrylate residue, and the carboxyl group is grafted to the side chain via an ester bond. Grafting via ester bonds and urethane bonds can also be carried out by known methods.
[0111] The structural unit (AE) is a structural unit that is optionally introduced for the purposes of adjusting the molecular weight and adjusting the amounts of each functional group, ie, the ultraviolet absorbing group, the polymerizable unsaturated group, and the carboxy group.
[0112] The structural unit (AE) may be a structural unit derived from a monomer that does not have any of the above functional groups. In order to adjust the physical properties of the (meth)acrylic copolymer, the structural unit may be a structural unit to which a functional group different from the above functional groups has been grafted.
[0113] Each of the above structural units may be modified with an alkylene oxide or a lactone.
[0114] The (meth)acrylic copolymer may be a copolymer containing the structural unit (AB) and the structural unit (AC) as essential structural units and optionally containing the structural unit (AD) and the structural unit (AE), or may be a copolymer containing the structural unit (AD) as an essential structural unit and optionally containing the structural unit (AB), the structural unit (AC) and the structural unit (AE). The (meth)acrylic copolymer containing the structural unit (AB) and the structural unit (AC) as essential structural units is easy to synthesize because it does not require a process for introducing the structural unit (AD). The (meth)acrylic copolymer containing the structural unit (AD) as an essential structural unit is easy to adjust the amount of each functional group provided by the structural unit (AD), and thus easy to adjust the development speed, etc.
[0115] The (meth)acrylic copolymer preferably has a weight average molecular weight (Mw) of 1000 to 100000, more preferably 5000 to 70000, and even more preferably 10000 to 50000. When the weight average molecular weight (Mw) is 1000 or more, the adhesiveness can be improved when used as a composition for forming an adhesive layer. When the weight average molecular weight (Mw) is 100000 or less, the solution viscosity of the curable composition is easily adjusted to be suitable for application, application in a short time is possible, and adhesiveness is easily increased. The weight average molecular weight (Mw) of the (meth)acrylic copolymer can be a polystyrene-equivalent value measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by Tosoh Corporation).
[0116] In addition, the (meth)acrylic copolymer preferably has a ratio of the structural unit (AA) of 0.1 mol% to 90 mol%, more preferably 0.1 mol% to 89 mol%, even more preferably 1 mol% to 85 mol%, and particularly preferably 5 mol% to 80 mol% relative to the total structural units of 100 mol%. By making the ratio of the structural unit (AA) 0.1 mol% or more, it is possible to make the cured film more easily absorb ultraviolet light, and more effectively promote the alteration or decomposition of the cured film by irradiation with a 355 nm laser. By making the ratio of the structural unit (A) 90 mol% or less, it is possible to increase the amount of functional groups other than ultraviolet absorbing groups contained in the (meth)acrylic copolymer, and to sufficiently increase the hardness and alkali solubility of the adhesive layer.
[0117] In addition, the (meth)acrylic copolymer preferably has a maximum absorbance of 0.10 or more at a wavelength of 260 nm to 400 nm, more preferably 0.10 to 1.50, and even more preferably 0.15 to 1.30. When the absorbance is 0.10 or more, the adhesive layer can easily absorb ultraviolet light, and the change or decomposition of the cured film caused by the laser irradiation can be more effectively promoted. When the absorbance is 1.50 or less, the exposure sensitivity is maintained, and patterning becomes possible. The absorbance can be measured under the same conditions as those for measuring the molar absorption coefficient.
[0118] The (meth)acrylic copolymer preferably has an acid value of 20 mgKOH / g to 200 mgKOH / g, more preferably 30 mgKOH / g to 180 mgKOH / g, and even more preferably 50 mgKOH / g to 150 mgKOH / g. By setting the acid value to 20 mgKOH / g or more, it is possible to make it difficult for residues to remain during alkaline development. By setting the acid value to 200 mgKOH / g or less, it is possible to appropriately adjust the penetration of the alkaline developer into the composition and suppress peeling development caused by rapid penetration of the alkaline developer. The acid value can be determined by titration with a 1 / 10N-KOH aqueous solution using a potentiometric titration device "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).
[0119] From the same viewpoint, the (meth)acrylic copolymer preferably has a ratio of structural units having a carboxy group (the ratio of the total amount of structural units (AC) and structural units (AD)) relative to 100 mol% of all structural units of 3 mol% to 50 mol%, more preferably 5 mol% to 45 mol%, and even more preferably 7 mol% to 40 mol%.
[0120] The (meth)acrylic copolymer preferably has an acrylic equivalent of 300 g / eq to 3000 g / eq, more preferably 350 g / eq to 2500 g / eq, and even more preferably 400 g / eq to 2000 g / eq. By making the acrylic equivalent 300 g / eq or more, it becomes easier to incorporate an ultraviolet absorbing group and a carboxyl group into the same molecule. By making the acrylic equivalent 3000 g / eq or less, it is possible to ensure sensitivity even at a low exposure dose, and to form a good developed pattern.
[0121] From the same viewpoint, the (meth)acrylic copolymer preferably has a ratio of structural units having a polymerizable unsaturated group (the ratio of the total amount of structural units (AB) and structural units (AD)) relative to 100 mol% of all structural units of 3 mol% to 90 mol%, more preferably 5 mol% to 85 mol%, and even more preferably 7 mol% to 80 mol%.
[0122] The ultraviolet absorbing group equivalent, acid value, acrylic equivalent and ratio of each structural unit of the (meth)acrylic copolymer can be adjusted by the copolymerization ratio when each of the above-mentioned monomers is copolymerized.
[0123] For example, the (meth)acrylic copolymer may be a copolymer having the following structural units in the following ratios: Note that the following ratios are the ratios (units: mol %) of each structural unit relative to 100 mol % of all structural units in the (meth)acrylic copolymer.
[0124] Structural unit (AA) 0.1 mol% to 80 mol%; Structural unit (AB) 5 mol% to 70 mol%, Structural unit (AC) 3 mol% to 50 mol%; Preferably, Structural unit (AA) 6 mol% to 70 mol%, Structural unit (AB) 10 mol% to 60 mol%, Structural unit (AC) 5 mol% to 45 mol%.
[0125] Structural unit (AA) 0.1 mol% to 80 mol%; Structural unit (AB) 0.001 mol% to 70 mol%, Structural unit (AD) 3 mol% to 50 mol%; Preferably, Structural unit (AA) 6 mol% to 70 mol%, Structural unit (AB) 0.1 mol% to 60 mol%, Structural unit (AD) 5 mol% to 45 mol%; More preferably, Structural unit (AA) 16 mol% to 60 mol%, Structural unit (AB) 1 mol% to 50 mol%, Structural unit (AD) 7 mol% to 40 mol%.
[0126] Structural unit (AA) 50 mol% to 90 mol%, Structural unit (AD) 10 mol% to 50 mol% Preferably, Structural unit (AA) 55 mol% to 80 mol%, Structural unit (AD) 20 mol% to 45 mol%.
[0127] Structural unit (AA) 0.1 mol% to 90 mol%; Structural unit (AB) 3 mol% to 89 mol%, Structural unit (AC) 3 mol% to 49 mol%; Structural unit (AD) 0.001 mol% to 47 mol%; Preferably, Structural unit (AA) 6 mol% to 80 mol%, Structural unit (AB) 5 mol% to 80 mol%, Structural unit (AC) 5 mol% to 44 mol%; Structural unit (AD) 0.001 mol% to 40 mol%, More preferably, Structural unit (AA) 16 mol% to 70 mol%; Structural unit (AB) 7 mol% to 70 mol%, Structural unit (AC) 7 mol% to 39 mol%, Structural unit (AD) 0.001 mol% to 33 mol%.
[0128] Structural unit (AA) 0.1 mol% to 90 mol%; Structural unit (AB) 3 mol% to 90 mol%, Structural unit (AC) 3 mol% to 50 mol%; Structural unit (AE) 0.1 mol% to 90 mol%, Preferably, Structural unit (AA) 6 mol% to 80 mol%, Structural unit (AB) 5 mol% to 80 mol%, Structural unit (AC) 5 mol% to 45 mol%, Structural unit (AE) 0.1 mol% to 80 mol%, More preferably, Structural unit (AA) 16 mol% to 70 mol%; Structural unit (AB) 7 mol% to 70 mol%, Structural unit (AC) 7 mol% to 40 mol%, Structural unit (AE) 0.1 mol% to 70 mol%.
[0129] Structural unit (AA) 0.1 mol% to 80 mol%; Structural unit (AD) 3 mol% to 50 mol%; Structural unit (AE) 0.1 mol% to 80 mol%, Preferably, Structural unit (AA) 6 mol% to 70 mol%, Structural unit (AD) 5 mol% to 45 mol%; Structural unit (AE) 1 mol% to 70 mol%.
[0130] Structural unit (AA) 0.1 mol% to 90 mol%; Structural unit (AB) 0.001 mol% to 85 mol%, Structural unit (AD) 3 mol% to 50 mol%; Structural unit (AE) 0.1 mol% to 95 mol%, Preferably, Structural unit (AA) 6 mol% to 80 mol%, Structural unit (AB) 0.001 mol% to 80 mol%, Structural unit (AD) 5 mol% to 45 mol%; Structural unit (AE) 0.1 mol% to 85 mol%, More preferably, Structural unit (AA) 16 mol% to 70 mol%; Structural unit (AB) 0.001 mol% to 70 mol%, Structural unit (AD) 7 mol% to 40 mol% Structural unit (AE) 1 mol% to 70 mol%.
[0131] Structural unit (AA) 0.1 mol% to 90 mol%; Structural unit (AC) 0.1 mol% to 47 mol%; Structural unit (AD) 3 mol% to 49 mol%; Structural unit (AE) 0.1 mol% to 90 mol%, Preferably, Structural unit (AA) 6 mol% to 80 mol%, Structural unit (AC) 1 mol% to 40 mol%; Structural unit (AD) 5 mol% to 39 mol%; Structural unit (AE) 0.1 mol% to 80 mol%.
[0132] Structural unit (AA) 0.1 mol% to 90 mol%; Structural unit (AB) 3 mol% to 90 mol%, Structural unit (AC) 3 mol% to 49 mol%; Structural unit (AD) 0.001 mol% to 47 mol%; Structural unit (AE) 0.1 mol% to 90 mol%, Preferably, Structural unit (AA) 6 mol% to 80 mol%, Structural unit (AB) 5 mol% to 80 mol%, Structural unit (AC) 5 mol% to 44 mol%; Structural unit (AD) 0.001 mol% to 40 mol%, Structural unit (AE) 0.1 mol% to 80 mol%, More preferably, Structural unit (AA) 16 mol% to 70 mol%; Structural unit (AB) 7 mol% to 70 mol%, Structural unit (AC) 7 mol% to 39 mol%, Structural unit (AD) 0.001 mol% to 33 mol%, Structural unit (AE) 0.1 mol% to 70 mol%.
[0133] Specific examples of the (meth)acrylic copolymer include a copolymer in which the structural unit (AA) is a structural unit represented by the following general formula (A-1), the structural unit (AB) is a structural unit represented by the following general formula (A-2), the structural unit (AC) is a structural unit represented by the following general formula (A-3), and the structural unit (AE) is a structural unit represented by the following general formula (A-4).
[0134] [ka]
[0135] [ka]
[0136] [ka]
[0137] [ka]
[0138] In general formulas (A-1) to (A-4), R 11 ~R 14 and R 19 represents a hydrogen atom or a methyl group, of which a methyl group is preferred.
[0139] R 15 ~R 18 and R 20 ~R 21 represents a hydrocarbon group having 1 to 10 carbon atoms which may have a cyclic structure or an aromatic ring, may have a substituent, may have an ether bond, and may have an unsaturated bond.
[0140] Examples of the hydrocarbon group having 1 to 10 carbon atoms include divalent alkylene groups having a straight or branched chain, such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene groups; divalent hydrocarbon groups having an alicyclic structure, such as cyclohexylene, methylcyclohexylene, ethylcyclohexylene, dimethylcyclohexylene, diethylcyclohexylene, methylethylcyclohexylene, propylcyclohexylene, and methylpropylcyclohexylene groups; and divalent hydrocarbon groups having an aromatic group, such as phenylene, methylphenylene, ethylphenylene, dimethylphenylene, methylethylphenylene, and naphthylene groups. Of these, methylene and ethylene groups are preferred, and R 15 ~R 16 is preferably an ethylene group, and R 17 ~R 18 More preferably, the substituent is a methylene group. Examples of the substituent include a methyl group and a methoxy group.
[0141] m1 and m2 are 0 or 1, and preferably 0. m3 and m4 are 0, 1 or 2, and preferably 0.
[0142] R 22 R represents a hydrocarbon group having 1 to 30 carbon atoms, which may have a cyclic structure or an aromatic ring, may have a substituent, may be modified with an alkylene oxide, and may have one or two heteroatoms. 22is preferably a linear or branched alkyl group having 1 to 10 carbon atoms, an optionally substituted cycloalkyl group having 3 to 30 carbon atoms, or an optionally substituted aryl group having 6 to 30 carbon atoms.
[0143] Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group, etc. Examples of the cycloalkyl group having 3 to 30 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a norbornyl group, a dicyclopentanyl group, and adamantyl group, etc. Examples of the aryl group having 6 to 30 carbon atoms include a phenyl group, a biphenyl group, a 1-naphthyl group, a 2-naphthyl group, a 9-anthryl group, a 9-phenanthryl group, a 1-pyrenyl group, a 5-naphthacenyl group, a 1-indenyl group, a 2-azulenyl group, a 9-fluorenyl group, a terphenyl group, a quaterphenyl group, an o-, m-, and p-tolyl group, a xylyl group, an o-, m-, and p-cumenyl group, a mesityl group, a pentalenyl group, a binaphthalenyl group, a ternaphthalenyl group, a quaternaphthalenyl group, a heptalenyl group, a biphenylenyl group, an indacenyl group, and a fluoranthenyl group. Group, acenaphthylenyl group, aceanthryleneyl group, phenalenyl group, fluorenyl group, anthryl group, bianthracenyl group, teranthracenyl group, quaternanthracenyl group, anthraquinolyl group, phenanthryl group, triphenylenyl group, pyrenyl group, chrysenyl group, naphthacenyl group, pleiadenyl group, picenyl group, perylenyl group, pentaphenyl group, pentacenyl group, tetraphenylenyl group, hexacenyl group, rubicenyl group, coronenyl group, trinaphthylenyl group, heptaphenyl group, heptacenyl group, and pyrantrenyl group. Among these, methyl group and ethyl group are preferred, and methyl group is more preferred. In addition, examples of the above-mentioned substituent include methyl group and methoxy group.
[0144] X1 represents an epoxy acrylate residue having a secondary hydroxyl group, an ester bond, or a urethane bond. Of these, the ester bond and the urethane bond are preferred, and the ester bond is more preferred.
[0145] X2 and X3 independently represent an epoxy acrylate residue having a secondary hydroxyl group, an ester bond, or a urethane bond. Among these, a urethane bond is preferred.
[0146] It is preferable that X1 to X3 are different bonds or structures from each other.
[0147] U represents an ultraviolet absorbing group. The ultraviolet absorbing group may be any functional group having the structure exemplified as the ultraviolet absorbing group contained in the structural unit (AA).
[0148] * indicates the bonding site with other structural units.
[0149] The molar ratio of the structural units represented by general formula (A-1):(molar ratio of the structural units represented by general formula (A-2):(molar ratio of the structural units represented by general formula (A-3):(molar ratio of the structural units represented by general formula (A-4)) is 0.1 to 89:5 to 89:5 to 50:0.1 to 89. However, the preferred ranges of a:b:c:d can be the same as the preferred ranges of the structural units (AA), (AB), (AC) and (AE) described above.
[0150] Other specific examples of the (meth)acrylic copolymer include a copolymer in which the structural unit (AA) is a structural unit represented by the following general formula (A-5), the structural unit (AB) is a structural unit represented by the following general formula (A-6), the structural unit (AD) is a structural unit represented by the following general formula (A-7), and the structural unit (AE) is a structural unit represented by the following general formula (A-8).
[0151] [ka]
[0152] [ka]
[0153] [ka]
[0154] [ka]
[0155] In general formulas (A-5) to (A-8), R 31 ~R 34 and R 39 each independently represents a hydrogen atom or a methyl group. Among these, a methyl group is preferred.
[0156] R 35 ~R 38 each independently represents a hydrocarbon group having 1 to 10 carbon atoms which may have a cyclic structure or an aromatic ring, which may have a substituent, which may have an ether bond, and which may have an unsaturated bond.
[0157] Examples of the hydrocarbon group having 1 to 10 carbon atoms include divalent alkylene groups having a straight or branched chain, such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene groups; divalent hydrocarbon groups having an alicyclic structure, such as cyclohexylene, methylcyclohexylene, ethylcyclohexylene, dimethylcyclohexylene, diethylcyclohexylene, methylethylcyclohexylene, propylcyclohexylene, and methylpropylcyclohexylene groups; and divalent hydrocarbon groups having an aromatic group, such as phenylene, methylphenylene, ethylphenylene, dimethylphenylene, methylethylphenylene, and naphthylene groups. Of these, methylene and ethylene groups are preferred, and R 35 ~R 36 is preferably an ethylene group, and R 37 ~R 38 More preferably, the substituent is a methylene group. Examples of the substituent include a methyl group and a methoxy group.
[0158] m5 and m6 are 0 or 1, and are preferably 0.
[0159] R 40 R represents a hydrocarbon group having 1 to 10 carbon atoms which may have a cyclic structure or an aromatic ring, may have a substituent, may have an ether bond, and may have an unsaturated bond. 40 R is preferably an alkylene group having 1 to 10 carbon atoms which may have a carboxy group, a cycloalkylene group having 3 to 10 carbon atoms which may have a carboxy group, a cycloalkene group having 3 to 10 carbon atoms which may have a carboxy group, or an aryl group having 6 to 10 carbon atoms which may have a carboxy group. 40 Specific examples of 35 ~R 38 and cycloalkene groups having 3 to 10 carbon atoms, such as a cyclopropene group, a cyclobutene group, a cyclopentene group, a cyclohexene group, a cycloheptene group, and a cyclooctene group. An ethylene group and a propylene group are preferred, and an ethylene group is more preferred.
[0160] R 41 R represents a hydrocarbon group having 1 to 30 carbon atoms, which may have a cyclic structure or an aromatic ring, may have a substituent, may be modified with an alkylene oxide, and may have one or two heteroatoms. 41 is preferably an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms which may have a substituent, or an aryl group having 6 to 30 carbon atoms which may have a substituent.
[0161] Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group, etc. Examples of the cycloalkyl group having 3 to 30 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a norbornyl group, a dicyclopentanyl group, and adamantyl group, etc. Examples of the aryl group having 6 to 30 carbon atoms include a phenyl group, a biphenyl group, a 1-naphthyl group, a 2-naphthyl group, a 9-anthryl group, a 9-phenanthryl group, a 1-pyrenyl group, a 5-naphthacenyl group, a 1-indenyl group, a 2-azulenyl group, a 9-fluorenyl group, a terphenyl group, a quaterphenyl group, an o-, m-, and p-tolyl group, a xylyl group, an o-, m-, and p-cumenyl group, a mesityl group, a pentalenyl group, a binaphthalenyl group, a ternaphthalenyl group, a quaternaphthalenyl group, a heptalenyl group, a biphenylenyl group, an indacenyl group, and a fluoranthenyl group. Group, acenaphthylenyl group, aceanthryleneyl group, phenalenyl group, fluorenyl group, anthryl group, bianthracenyl group, teranthracenyl group, quaternanthracenyl group, anthraquinolyl group, phenanthryl group, triphenylenyl group, pyrenyl group, chrysenyl group, naphthacenyl group, pleiadenyl group, picenyl group, perylenyl group, pentaphenyl group, pentacenyl group, tetraphenylenyl group, hexacenyl group, rubicenyl group, coronenyl group, trinaphthylenyl group, heptaphenyl group, heptacenyl group, and pyrantrenyl group. Among these, methyl group and ethyl group are preferred, and methyl group is more preferred. In addition, examples of the above-mentioned substituent include methyl group and methoxy group.
[0162] X4 represents an epoxy acrylate residue having a secondary hydroxyl group, an ester bond, or a urethane bond. Among these, an ester bond is preferred.
[0163] U represents an ultraviolet absorbing group. The ultraviolet absorbing group may be any functional group having the structure exemplified as the ultraviolet absorbing group contained in the structural unit (AA).
[0164] * indicates the bonding site with other structural units.
[0165] The molar ratio of the structural units represented by general formula (A-5):(molar ratio of the structural units represented by general formula (A-6):(molar ratio of the structural units represented by general formula (A-7):(molar ratio of the structural units represented by general formula (A-8)) is 0.1-90:0.001-50:5-50:0.1-94. However, the preferred ranges of e:f:g:h can be the same as the preferred ranges of the structural units (AA), (AB), (AD) and (AE) described above.
[0166] The (meth)acrylic copolymer can be synthesized by copolymerizing an appropriate combination of the following monomers, and then grafting an ultraviolet absorbing group, a polymerizable unsaturated group, or a carboxy group onto the side chains of the structural units derived from the monomers (Ax1) to (Ax3). (Aa) A monomer having a (meth)acryloyl group and an ultraviolet absorbing group (Ac) A monomer having a (meth)acryloyl group and a carboxy group (Ae) A monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxy group. (Ax1) A monomer having a (meth)acryloyl group and a hydroxyl group (Ax2) A monomer having a (meth)acryloyl group and an isocyanate group (Ax3) A monomer having a (meth)acryloyl group and a glycidyl group or an alicyclic epoxy group
[0167] The monomer (Aa) is a monomer for introducing an ultraviolet absorbing group into the (meth)acrylic copolymer.
[0168] From the viewpoint of increasing the ultraviolet absorbing ability of the (meth)acrylic copolymer, it is preferable that the monomer (Aa) is a monomer having a molar absorption coefficient at a wavelength of 355 nm of 3000 L / (mol·cm) or more. From the same viewpoint, it is more preferable that the monomer (Aa) is a monomer having a molar absorption coefficient at a wavelength of 355 nm of 3000 L / (mol·cm) to 100000 L / (mol·cm), further preferably a monomer having a molar absorption coefficient at a wavelength of 355 nm of 4000 L / (mol·cm) to 90000 L / (mol·cm), and particularly preferably a monomer having a molar absorption coefficient at a wavelength of 5000 L / (mol·cm) to 80000 L / (mol·cm). The molar absorption coefficient can be measured under the same conditions as those for measuring the molar absorption coefficient described above.
[0169] Examples of monomer (Aa) include compounds described in JP-A-2004-182924, JP-A-2007-286123, JP-A-2007-331359, JP-A-2013-204001, JP-A-2015-124254, JP-A-2019-137844, and JP-A-2020-189906.
[0170] The monomer (Ac) is a monomer for introducing a carboxy group into the (meth)acrylic copolymer. The monomer (Ac) is preferably a monomer that does not have the above-mentioned ultraviolet absorbing group. The monomer (Ac) is preferably a monomer that has a molar absorption coefficient at a wavelength of 355 nm of less than 3000 L / (mol cm). The molar absorption coefficient can be measured under the same conditions as those for measuring the molar absorption coefficient described above.
[0171] Examples of monomers (Ac) include (meth)acrylic acid, succinic acid mono(2-(meth)acryloyloxyethyl), hexahydrophthalic acid(2-(meth)acryloyloxyethyl), phthalic acid(2-(meth)acryloyloxyethyl), maleic acid(2-(meth)acryloyloxyethyl), fumaric acid(2-acryloyloxyethyl), itaconic acid(2-(meth)acryloyloxyethyl). , citraconic acid (2-(meth)acryloyloxyethyl), carboxyethyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, mono n-butyl maleate (2-(meth)acryloyloxyethyl), mono n-butyl fumarate (2-(meth)acryloyloxyethyl), and mono n-butyl itaconate (2-(meth)acryloyloxyethyl).
[0172] The monomer (Ae) is a monomer for adjusting the molecular weight and the amount of functional groups of the (meth)acrylic copolymer.
[0173] Examples of the monomer (Ae) include those having an alkyl chain having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, such as ethyl (meth)acrylate, methyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate. (Meth)acrylate, methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, 2-ethylhexyl diglycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate and other alkylene oxide-modified (meth)acrylates having an alkyl chain having 1 to 10 carbon atoms, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantan-1-yl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, 3,3,(Meth)acrylates having alicyclic hydrocarbons with 3 to 30 carbon atoms, such as 5-trimethylcyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenylethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-biphenyl (meth)acrylate, (meth)acrylates having aromatic hydrocarbons with 3 to 30 carbon atoms, such as 2-naphthyl (meth)acrylate, neopentyl glycol-acrylic acid-benzoic acid ester, phenoxyethylene glycol methacrylate, ethoxylated-O-phenyl Examples of the (meth)acrylate include alkylene oxide-modified aromatic hydrocarbon having 3 to 30 carbon atoms, such as phenol (meth)acrylate, phthalimide (meth)acrylate, maleimide (meth)acrylate, benzophenone (meth)acrylate, 2-hydroxy-4-(meth)acryloyloxybenzophenone, and hydroxy-4-(2-(meth)acryloyloxy)ethoxybenzophenone, and other (meth)acrylates having a hydrocarbon group having 1 to 30 carbon atoms which may have one or two heteroatoms.
[0174] The monomers (Ax1) to (Ax3) are monomers for introducing the above-mentioned functional group into the side chain of the (meth)acrylic copolymer by grafting.
[0175] The monomers (Ax1) to (Ax3) are preferably monomers that do not have the above-mentioned ultraviolet absorbing group. Moreover, the monomers (Ax1) to (Ax3), and the monomer (Aa) are preferably monomers that have a molar absorption coefficient at a wavelength of 355 nm of less than 3000 L / (mol cm). Moreover, the monomers (Ax1) to (Ax3) are preferably monomers that do not have a carboxy group. The molar absorption coefficient can be measured under the same conditions as those for measuring the molar absorption coefficient described above.
[0176] For example, a monomer (Ax1) having a hydroxyl group can be used, after copolymerization with other monomers, to introduce a polymerizable unsaturated group into a (meth)acrylic copolymer via a urethane bond by reacting a compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group with the hydroxyl group.
[0177] Alternatively, the monomer (Ax1) having a hydroxyl group can be used for introducing a carboxyl group into the (meth)acrylic copolymer via an ester bond by reacting the hydroxyl group with (Ay1b) a dicarboxylic acid or an acid monoanhydride thereof after copolymerization with another monomer.
[0178] Examples of such monomers (Ax1) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, and ethyl-α-hydroxymethyl acrylate.
[0179] Examples of the compound having an isocyanate group and a polymerizable unsaturated group (Ay1a), which is used together with the monomer (Ax1), include (2-(meth)acryloyloxyethyl)isocyanate.
[0180] Examples of the dicarboxylic acid (Ay1b) or the acid monoanhydride thereof used together with the monomer (Ax1) include open-chain hydrocarbon dicarboxylic acids, alicyclic hydrocarbon dicarboxylic acids, aromatic hydrocarbon dicarboxylic acids, and the acid monoanhydrides thereof.
[0181] Examples of the above-mentioned chain hydrocarbon dicarboxylic acid and tricarboxylic acid include succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, and diglycolic acid, as well as these dicarboxylic acids having any substituent introduced therein.
[0182] Examples of the alicyclic hydrocarbon dicarboxylic acid include cyclobutane dicarboxylic acid, cyclopentane dicarboxylic acid, hexahydrophthalic acid, tetrahydrophthalic acid, methyl tetrahydrophthalic acid, methyl end methylene tetrahydrophthalic acid, chlorendic acid, and norbornane dicarboxylic acid, as well as dicarboxylic acids having any substituent introduced therein.
[0183] Examples of the aromatic hydrocarbon dicarboxylic acid include phthalic acid, isophthalic acid, 1,8-naphthalenedicarboxylic acid, and 2,3-naphthalenedicarboxylic acid, as well as these dicarboxylic acids having any desired substituent introduced therein.
[0184] Of these, the dicarboxylic acids are preferably succinic acid, itaconic acid, tetrahydrophthalic acid, and phthalic acid, and more preferably succinic acid, itaconic acid, and tetrahydrophthalic acid.
[0185] It is preferable to use the dicarboxylic acid as its monoanhydride.
[0186] Instead of the compound having an isocyanate group and a polymerizable unsaturated group (Ay1a), a compound having an isocyanate group and an ultraviolet absorbing group or a compound having an isocyanate group and a carboxy group may be used to introduce the ultraviolet absorbing group or the carboxy group into the side chain of the structural unit derived from the monomer (Ax1) via a urethane bond.
[0187] In addition, instead of (Ay1b) dicarboxylic acid or its monoanhydride, a compound having a carboxy group and an ultraviolet absorbing group, or a compound having a carboxy group and a polymerizable unsaturated group may be used to introduce the ultraviolet absorbing group or the polymerizable unsaturated group into the side chain of the structural unit derived from the monomer (Ax1) via a urethane bond.
[0188] In addition, the monomer (Ax2) having an isocyanate group can be used for introducing a polymerizable unsaturated group into the (meth)acrylic copolymer via a urethane bond by reacting (Ay2) a compound having a hydroxyl group and a polymerizable unsaturated group with the isocyanate group after copolymerization with other monomers.
[0189] Examples of such a monomer (Ax2) include the compounds exemplified above as the compound having an isocyanate group and a polymerizable unsaturated group.
[0190] Examples of the compound (y2) having a hydroxyl group and a polymerizable unsaturated group, which is used together with the monomer (Ax2), include the compounds exemplified as the monomer (Ax1).
[0191] Instead of the compound having a hydroxyl group and a polymerizable unsaturated group (Ay2), a compound having a hydroxyl group and an ultraviolet absorbing group or a compound having a hydroxyl group and a carboxy group may be used to introduce the ultraviolet absorbing group or the carboxy group into the side chain of the structural unit derived from the monomer (Ax2) via a urethane bond.
[0192] Furthermore, the monomer (Ax3) having a glycidyl group or an alicyclic epoxy group can be used for introducing a polymerizable unsaturated group into the (meth)acrylic copolymer via an epoxy acrylate residue by reacting (Ay3) a compound having a carboxy group and a polymerizable unsaturated group with the glycidyl group or the alicyclic epoxy group after copolymerization with other monomers.
[0193] Examples of such monomers (Ax3) include glycidyl (meth)acrylate, β-propyl glycidyl (meth)acrylate, β-methyl glycidyl-α-ethyl (meth)acrylate, 3-methyl-3,4-epoxybutyl (meth)acrylate, 4-methyl-4,5-epoxypentyl (meth)acrylate, 5-methyl-5,6-epoxyhexyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl methacrylate.
[0194] Examples of the compound (Ay3) having a carboxy group and a polymerizable unsaturated group, which is used together with the monomer (Ax3), include the compounds exemplified as the monomer (Ac).
[0195] In addition, the epoxy acrylate residue generated from the monomer (Ax3) may be further reacted with a polyvalent carboxylic acid or anhydride thereof (Az3) to introduce a carboxy group into the (meth)acrylic copolymer via the epoxy acrylate residue.
[0196] Examples of polyvalent carboxylic acids to be reacted with the epoxy acrylate residue include the dicarboxylic acids or their monoanhydrides exemplified as the monomer (Ay1b), as well as tricarboxylic acids or their monoanhydrides and tetracarboxylic acids or their dianhydrides.
[0197] Examples of the tricarboxylic acid include trimellitic acid and hexahydrotrimellitic acid.
[0198] Examples of the tetracarboxylic acid include chain hydrocarbon tetracarboxylic acids, alicyclic hydrocarbon tetracarboxylic acids, aromatic tetracarboxylic acids, and the like.
[0199] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and chain hydrocarbon tetracarboxylic acids having a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group introduced therein.
[0200] Examples of the alicyclic hydrocarbon tetracarboxylic acid include cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, and alicyclic tetracarboxylic acids having a substituent such as a chain hydrocarbon group or an unsaturated hydrocarbon group introduced therein.
[0201] Examples of aromatic tetracarboxylic acids include pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid.
[0202] It is preferable to use the above tetracarboxylic acid as its acid dianhydride.
[0203] For example, a copolymer having the structural unit (AA) represented by the above general formula (A-1), the structural unit (AB) represented by the above general formula (A-2), the structural unit (AC) represented by the above general formula (A-3), and the structural unit (AE) represented by the above general formula (A-4) can be synthesized by the following steps.
[0204] [Process (1)-1] (Aa) a monomer having a (meth)acryloyl group and an ultraviolet absorbing group; (Ac) a monomer having a (meth)acryloyl group and a carboxy group; (Ae) a monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxy group; (Ax1) a monomer having a (meth)acryloyl group and a hydroxyl group; A process for obtaining a copolymer by copolymerizing the above.
[0205] [Process (1)-2] A step of reacting the copolymer obtained in step (1)-1 with a compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group to form a urethane bond between the hydroxyl group derived from the monomer (Ax1) and the isocyanate group of the compound (Ay1a), thereby grafting the polymerizable unsaturated group onto the copolymer.
[0206] The copolymerization in step (1)-1 can be carried out by mixing the monomers to be copolymerized together with a thermal polymerization initiator in a solvent and reacting them. The reaction temperature depends on the type of the thermal polymerization initiator used, but it is preferable to carry out the reaction in the solvent for 2 to 12 hours at a temperature range of 60 to 100°C.
[0207] The thermal polymerization initiator may be any common thermal radical polymerization initiator, and is preferably an azo compound or a peroxide, more preferably an azo compound from the viewpoint of producing a linear polymer.
[0208] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(dimethylisobutyrate), etc. Among them, 2,2'-azobis(2,4-dimethylvaleronitrile) is preferred from the viewpoint of reaction temperature.
[0209] The solvent can be appropriately selected from those used in resin compositions. Examples of the solvent that can be used include alcohols, glycols, aliphatic cyclic ketones, and acetates. Of these, it is preferable to use a solvent other than alcohols.
[0210] Examples of glycols include ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.
[0211] Examples of the aliphatic cyclic ketones include cyclohexanone, ortho-methylcyclohexanone, meta-methylcyclohexanone, and para-methylcyclohexanone.
[0212] Examples of acetate esters include ethyl acetate, n-propyl acetate, and n-butyl acetate.
[0213] In addition to these, saturated hydrocarbon solvents such as solvent naphtha, methyl ethyl ketone, methyl isobutyl ketone, n-octane, and isooctane, as well as ethyl cellosolve, butyl cellosolve, and the like may be used.
[0214] In this case, it is preferable not to use a solvent containing a hydroxyl group such as isopropyl alcohol (IPA) or propylene glycol monomethyl ether (PGME), etc. This avoids the reaction of the isocyanate group of the compound having an isocyanate group and a polymerizable unsaturated group (Ay1a) with the hydroxyl group of the solvent in the next step, and allows the reaction to form a urethane bond to proceed reliably and sufficiently.
[0215] The amount of the solvent is preferably 10 to 2000 parts by weight, and more preferably 50 to 500 parts by weight, per 100 parts by weight of the total of the monomers to be copolymerized mixed in the above range.
[0216] In the reaction of step (1)-2, it is preferable to mix the monomer (Ay1a) (a compound having an isocyanate group and a polymerizable unsaturated group) with the reaction solution obtained in the above-mentioned step (1)-1, and then react them in a solvent at a temperature range of 40° C. to 100° C. for 2 to 12 hours.
[0217] The solvent can be appropriately selected from the above-mentioned solvents. The reaction can be carried out by adding a catalyst as necessary. Examples of the catalyst include tin compounds or titanium compounds, and amine compounds. Specific examples of the catalyst include dibutyltin laurate, tetra n-butoxytitanium, and triethylamine. Of these, tin compounds are more preferable because the reaction can be easily controlled. The amount of catalyst added is preferably 0.01 to 10 parts by weight based on a total of 100 parts by weight of the monomer (Ay1a) isocyanate group and the compound having a polymerizable unsaturated group. At this time, it is preferable not to polymerize the (meth)acryloyl group of the monomer (Ay1a) isocyanate group and the compound having a polymerizable unsaturated group, and a polymerization inhibitor or the like may be added for this purpose.
[0218] The compound having an isocyanate group and a polymerizable unsaturated group in the monomer (Ay1a) is preferably reacted under conditions in which the number of moles of the isocyanate group is less than the number of moles of the hydroxyl group derived from the monomer (Ax1). Specifically, the number of moles of the isocyanate group derived from the monomer (Ay1a) is more preferably 95 to 99% of the number of moles of the hydroxyl group derived from the monomer (Ax1).
[0219] The materials used may be changed appropriately depending on the constitution of each structural unit contained in the resulting polymer.
[0220] In addition, a copolymer having the structural unit (AA) represented by the above general formula (A-5), the structural unit (AB) represented by the above general formula (A-6), the structural unit (AD) represented by the above general formula (A-7), and the structural unit (AE) represented by the above general formula (A-8) can be synthesized by the following process.
[0221] [Process (2)-1] (Aa) a monomer having a (meth)acryloyl group and an ultraviolet absorbing group; (Ae) a monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxy group; (Ax3) a monomer having a (meth)acryloyl group and a glycidyl group or an alicyclic epoxy group; A process for obtaining a copolymer by copolymerizing the above.
[0222] [Process (2)-2] A step of reacting the copolymer obtained in step (2)-1 with a compound (Ay3) having a carboxy group and a polymerizable unsaturated group to form an epoxy acrylate residue by a reaction between the glycidyl group or alicyclic epoxy group derived from the monomer (Ax3) and the carboxy group of the compound (Ay3), thereby grafting the polymerizable unsaturated group onto the copolymer.
[0223] [Process (2)-3] a step of reacting the copolymer having the polymerizable unsaturated groups grafted thereto in the step (2)-2 with a polyvalent carboxylic acid or anhydride thereof (Az3) to further graft a carboxy group onto the copolymer by a reaction between a hydroxyl group derived from the monomer (Ax1) or an epoxy acrylate residue formed by the reaction between the monomer (Ax3) and the monomer (Ay3) and a carboxy group or a carboxylic anhydride group possessed by the compound (Az3).
[0224] The copolymerization in step (2)-1 can be carried out in the same manner as the copolymerization in step (1)-1 described above. The reaction temperature depends on the type of the thermal polymerization initiator used, but it is preferable to carry out the reaction in a solvent for 2 to 12 hours at a temperature range of, for example, 60 to 100°C.
[0225] The thermal polymerization initiator may be any common thermal radical polymerization initiator, and is preferably an azo compound or a peroxide, more preferably an azo compound from the viewpoint of producing a linear polymer.
[0226] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(dimethylisobutyrate), etc. Among them, 2,2'-azobis(2,4-dimethylvaleronitrile) is preferred from the viewpoint of reaction temperature.
[0227] The solvent can be appropriately selected from those used in resin compositions. Examples of the solvent that can be used include alcohols, glycols, aliphatic cyclic ketones, and acetates. Of these, it is preferable to use a solvent other than alcohols.
[0228] Examples of glycols include ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.
[0229] Examples of the aliphatic cyclic ketones include cyclohexanone, ortho-methylcyclohexanone, meta-methylcyclohexanone, and para-methylcyclohexanone.
[0230] Examples of acetate esters include ethyl acetate, n-propyl acetate, and n-butyl acetate.
[0231] In addition to these, saturated hydrocarbon solvents such as solvent naphtha, methyl ethyl ketone, methyl isobutyl ketone, n-octane, and isooctane, as well as ethyl cellosolve, butyl cellosolve, and the like may be used.
[0232] In this case, by not using a solvent containing a hydroxyl group, such as isopropyl alcohol (IPA) or propylene glycol monomethyl ether (PGME), it is possible to avoid a reaction between the acid anhydride group of the polyvalent carboxylic acid (Az3) or its anhydride and the hydroxyl group of the solvent in the next step, and to ensure that the reaction to form an ester bond is carried out reliably and sufficiently.
[0233] The amount of the solvent is preferably 10 to 2000 parts by weight, and more preferably 50 to 500 parts by weight, per 100 parts by weight of the total of the monomers to be copolymerized mixed in the above range.
[0234] The reaction of step (2)-2 can be carried out in a solvent at a reaction temperature in the range of 80 to 130° C. for 5 to 18 hours. The reaction can be efficiently carried out by adding a base catalyst. Examples of the base catalyst include ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, and phosphines such as triphenylphosphine and tris(2,6-dimethoxyphenyl)phosphine.
[0235] The reaction in step (2)-3 can be carried out in a solvent at a reaction temperature in the range of 80 to 130° C. for 5 to 48 hours to form the compound.
[0236] In step (2)-1, a monomer (Ax1) having a (meth)acryloyl group and a hydroxyl group may be copolymerized, and in step (2)-3, an ester bond may be formed between the hydroxyl group derived from the monomer (Ax1) and the carboxyl group or carboxylic anhydride group of the compound (Az3) to graft the carboxyl group onto the copolymer. The reaction conditions in this case may be the same as those in step (2)-3.
[0237] Incidentally, the monomers and compounds exemplified in the above synthesis method are merely examples, and it goes without saying that other monomers and compounds having similar functional groups can also be used.
[0238] In the adhesive layer-forming composition of the present embodiment, the content of the above-mentioned (meth)acrylic copolymer is preferably 10% by mass to 80% by mass, more preferably 30% by mass to 80% by mass, and even more preferably 50% by mass to 80% by mass, based on the total mass of the solid content. If the content of the above-mentioned (A) component is 10% by mass or more based on the total mass of the solid content, it is likely to absorb irradiated light (e.g., ultraviolet light) and change in quality, so that the support and the adherend can be easily separated. If the content is 80% by mass or less, the acidic groups for expressing alkali solubility can be sufficiently consumed by the crosslinking reaction with the (B) component, so that the alkali resistance can be improved.
[0239] 1-2.(B) Epoxy compounds having at least two epoxy groups The adhesive layer-forming composition according to this embodiment contains the component (B) in an amount of 25% by mass to 70% by mass relative to the total mass of the unsaturated group-containing alkali-soluble resin, the component (A).
[0240] By making the content of the (B) component 25% by mass or more based on the total mass of the (A) component, it is possible to sufficiently increase the alkali resistance, while by making the content 70% by mass or less, it is possible to prevent the crosslink density of the adhesive layer after curing from becoming excessively high, and it is possible to maintain toughness, thereby increasing the adhesive strength.
[0241] In addition, the (B) component preferably has an aromatic ring or an alicyclic structure, and more preferably has an aromatic ring structure. By having an aromatic ring or an alicyclic structure, it is possible to suppress the penetration of an alkaline stripping solution into the adhesive layer, thereby improving the alkali resistance. By having an aromatic ring, Furthermore, the alkali resistance can be improved.
[0242] In addition, the absorbance of the (B) component at a wavelength of 266 nm is preferably 0.10 or more, more preferably 0.10 to 1.00, even more preferably 0.20 to 1.00, and most preferably 0.25 to 1.00. By making the (B) component have an absorbance at 266 nm of 0.10 or more, the processability (peelability) of the adhesive layer by a 266 nm laser can be improved. In addition, by making the (B) component have an absorbance at 266 nm of 1.00 or less, the adhesive layer is prevented from becoming excessively hard, and both adhesive strength and laser processability can be achieved. The absorbance can be a value measured by using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation) to measure the absorbance of an acetonitrile solution having a concentration of 0.001% by weight in a quartz cell with an optical path length of 1 cm.
[0243] Examples of the component (B) include bisphenol A type epoxy compounds (e.g., jER 828: manufactured by Mitsubishi Chemical Corporation, Showfree BATG: manufactured by Resonac Corporation), bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds (e.g., EPPN-501H: manufactured by Nippon Kayaku Co., Ltd.), phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy compounds (e.g., jER YX4000: manufactured by Mitsubishi Chemical Corporation), naphthol aralkyl type epoxy compounds, trisphenolmethane type epoxy compounds, tetrakisphenolethane type epoxy compounds, glycidyl ethers of polyhydric alcohols (e.g., Epolite 100MF: manufactured by Kyoeisha Chemical Co., Ltd.), glycidyl esters of polycarboxylic acids, copolymers of monomers having (meth)acrylic groups containing glycidyl (meth)acrylate as a unit, such as copolymers of methacrylic acid and glycidyl methacrylate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate (e.g., Celloxide 2021P: manufactured by Daicel Corporation), butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε-caprolactone (e.g., Epolead GT401: manufactured by Daicel Corporation), epoxy compounds having epoxycyclohexyl groups such as HiREM-1 manufactured by Shikoku Kasei Kogyo Co., Ltd., polyfunctional epoxy compounds having a dicyclopentadiene skeleton (e.g., HP7200 series: manufactured by DIC Corporation), 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (e.g., EHPE3150: manufactured by Daicel Corporation), epoxidized polybutadiene (e.g., NISSO-PB·JP-100: manufactured by Nippon Soda Co., Ltd.), and epoxy compounds having a silicone skeleton.
[0244] Among the (B) components, epoxy compounds containing an alicyclic structure and epoxy compounds containing an aromatic ring structure are preferred, and epoxy compounds containing an aromatic ring structure are more preferred. By using such a (B) component, the solubility in an alkaline stripping solution when cured is likely to decrease, and the resistance to an alkaline stripping solution is likely to increase. In addition, among the epoxy compounds containing an aromatic ring structure, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, biphenyl type epoxy compounds, and fluorene type epoxy compounds are preferred, and biphenyl type epoxy compounds and fluorene type epoxy compounds are more preferred. Biphenyl type epoxy compounds and fluorene type epoxy compounds have a structure in which aromatic rings are conjugated, and have high absorbance. Therefore, biphenyl type epoxy compounds and fluorene type epoxy compounds can improve the laser peelability of the adhesive layer.
[0245] The epoxy equivalent of the epoxy compound of component (B) is preferably 100 g / eq to 300 g / eq, more preferably 100 g / eq to 250 g / eq. The number average molecular weight (Mn) of the epoxy compound of component (B) is preferably 100 to 5000. When the epoxy equivalent is 100 g / eq to 300 g / eq and the number average molecular weight (Mn) of the epoxy compound is 100 to 5000, a cured film having good solvent resistance can be obtained. When the epoxy equivalent is 300 g / eq or less, the alkali resistance can be further improved. Note that these compounds may be used alone or in combination of two or more kinds.
[0246] The content of the (B) component is 25% by mass to 70% by mass, preferably 25% by mass to 60% by mass, and more preferably 30% by mass to 60% by mass, based on the total mass of the (A) component. By making it 25% by mass or more, a sufficient crosslinked structure can be formed, so that the alkali resistance can be further improved. Also, if it is 70% by mass or less, no unreacted (B) component remains in the adhesive layer after curing, and the toughness of the adhesive layer can be maintained, so that the adhesive strength can be increased.
[0247] The content of the (B) component is preferably more than 0% by mass and not more than 41% by mass, more preferably 3% to 41% by mass, and even more preferably 15% to 41% by mass, based on the total mass of the solids. When the (E) component is 15% by mass or more based on the total mass of the solids, a sufficient crosslinked structure can be formed, improving chemical resistance. When the (E) component is 41% by mass or less, no unreacted (B) component remains in the adhesive layer after curing, and toughness can be maintained, thereby increasing adhesive strength.
[0248] 1-3. (C) Polymerizable compound having at least one ethylenically unsaturated bond The polymerizable compound (C) having at least one ethylenically unsaturated bond (hereinafter also referred to as "component (C)") enhances the adhesive strength to an adherend and the solvent resistance of the cured film obtained by curing the curable composition. Component (C) may have one or more polymerizable unsaturated groups that can react (polymerize) with the polymerizable unsaturated groups of component (A) or other molecules of component (C).
[0249] From the viewpoint of increasing adhesive strength, the component (C) is preferably liquid at 25° C. When the component (C) is liquid at 25° C., the liquidity of the coating film of the composition for forming an adhesive layer is increased. As a result, when the support and the adherend are adhered to each other via the adhesive layer, the conformability of the coating film to the support and the adherend is increased, and the adhesive strength is increased.
[0250] The content of the (C) component is preferably 1% by mass to 20% by mass, more preferably 1% by mass to 10% by mass, and even more preferably 1% by mass to 5% by mass, based on the total mass of the (A) component and the (B) component. When the content of the (C) component is 1% by mass or more based on the total mass of the (A) component and the (B) component, the liquidity of the coating film of the adhesive layer-forming composition is increased. As a result, when the support and the adherend are bonded via the adhesive layer, the conformability of the coating film to the support and the adherend is increased, and the adhesive strength is increased. When the content is 20% by mass or less, the excessive increase of a highly flexible crosslinked structure can be suppressed, and the alkali resistance can be increased. In addition, the content of the (A) component and the (B) component, which have high laser absorptivity, increases relatively, and the laser processability can also be improved. When the content is 10% by mass or less, the alkali resistance and the laser processability can be further improved.
[0251] The content of the (C) component is preferably 1% by mass to 25% by mass, more preferably 1% by mass to 13% by mass, and even more preferably 1% by mass to 7% by mass, based on the mass of the (A) component. When the content of the (C) component is 1% by mass or more based on the mass of the (A) component, the liquidity of the coating film of the adhesive layer-forming composition is increased. This increases the conformability of the coating film to the support and the adherend when adhering the support and the adherend via the adhesive layer, thereby increasing the adhesive strength. When the content is 25 parts by mass or less, excessive increase of a highly flexible crosslinked structure can be suppressed, and alkali resistance can be increased.
[0252] The polymerizable unsaturated group is preferably the same functional group as the polymerizable unsaturated group of the (A) component. Specifically, the polymerizable unsaturated group is preferably a (meth)acryloyl group. The (C) component may be a monomer, an oligomer, or a polymer. The (C) component is preferably a monomer or an oligomer.
[0253] Examples of the component (C) include (meth)acrylic acid esters such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, sorbitol penta(meth)acrylate, sorbitol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; Examples of the epoxy (meth)acrylate include urethane acrylate monomers such as rithritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene isocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer; epoxy (meth)acrylates such as bisphenol A type epoxy (meth)acrylate, bisphenol F type epoxy (meth)acrylate, bisphenol fluorene type epoxy (meth)acrylate, diphenyl fluorene type epoxy (meth)acrylate, phenol novolac type epoxy (meth)acrylate, cresol novolac type epoxy (meth)acrylate, and phenol aralkyl type epoxy (meth)acrylate; and dendritic polymers having a (meth)acrylic group.
[0254] The component (C) preferably has two or more (meth)acryloyl groups, and more preferably has three or more (meth)acryloyl groups. When the component (C) has two or more (meth)acryloyl groups, the crosslink density is improved, and the solvent resistance of the coating film or cured film is improved.
[0255] The acrylic equivalent of the (C) component is preferably 50 g / eq to 500 g / eq, more preferably 70 g / eq to 400 g / eq, and even more preferably 70 g / eq to 300 g / eq. When the acrylic equivalent of the photopolymerizable compound is 500 g / eq or less, the sensitivity to radiation (e.g., ultraviolet light) is high. In addition, the crosslink density is increased, so that the alkali resistance can be increased. When the acrylic equivalent is 400 g / eq or less, the alkali resistance can be further increased, and when the acrylic equivalent is 300 g / eq or less, the alkali resistance can be further increased. When the acrylic equivalent is 50 g / eq or more, the crosslink density is not too high, and the laser peelability is improved. The acrylic equivalent of the photopolymerizable compound can be determined, for example, by dividing the molecular weight by the number of acrylic functional groups. In addition, the weight average molecular weight (Mw) of the photopolymerizable compound can be determined, for example, by using the above-mentioned gel permeation chromatography (GPC) "HLC-8220GPC".
[0256] From the viewpoint of further improving the adhesion of the cured film to the adherend, the (C) component may contain an alkylene oxide-modified or lactone-modified compound. When an alkylene oxide-modified or lactone-modified compound is used as the (C) component, the content is preferably 1% by mass to 15% by mass, more preferably 1% by mass to 10% by mass, and even more preferably 1% by mass to 5% by mass, based on the total mass of the (A) component and the (B) component. When the content of the (C) component is 1% by mass or more based on the total mass of the (A) component and the (B) component, the liquidity of the coating film of the adhesive layer-forming composition is increased. As a result, when the support and the adherend are bonded via the adhesive layer, the conformability of the coating film to the support and the adherend is increased, and the adhesive strength is increased. When the content is 15 parts by mass or less, the excessive increase of a highly flexible crosslinked structure can be suppressed, and the alkali resistance can be increased.
[0257] As component (C), a mixture of an alkylene oxide-modified or lactone-modified compound and a compound not containing an alkylene oxide-modified site or a lactone-modified site may be used. In this case, from the viewpoint of increasing the crosslink density and improving the alkali resistance, the content of the compound not containing an alkylene oxide-modified site or a lactone-modified site is preferably 75% by mass to 100% by mass, more preferably 85% by mass to 100% by mass, and even more preferably 95% by mass to 100% by mass, based on the total mass of component (C).
[0258] The alkylene oxide modified product is preferably a compound having an alkylene oxide group having 2 to 6 carbon atoms, more preferably a compound having an alkylene oxide group having 2 to 4 carbon atoms, and even more preferably a compound having an alkylene oxide group having 2 to 3 carbon atoms.
[0259] The alkylene oxide modified product is preferably a compound in which 1 to 15 moles of alkylene oxide are added to 1 mole of a compound having a plurality of polymerizable unsaturated groups, such as those shown in the examples of the component (C), more preferably a compound in which 2 to 10 moles of alkylene oxide are added, and most preferably a compound in which 2 to 8 moles of alkylene oxide are added. By adding 1 mole or more of alkylene oxide, the fluidity of the curable composition can be increased and good adhesive strength can be obtained. In addition, by making the amount 15 moles or less, the crosslinking density can be appropriately reduced while maintaining the adhesive strength, so that good laser releasability can be obtained, and by making the amount 10 moles or less, even better laser releasability can be obtained.
[0260] The lactone modified product has a structure in which lactone having 2 to 6 carbon atoms is ring-opened (-C(=O)-(CH2) k -O-, k is a number one less than the number of carbon atoms in the lactone), more preferably a compound having a ring-opened structure of a lactone having 4 to 6 carbon atoms, and even more preferably a compound having a ring-opened structure of a lactone having 6 carbon atoms.
[0261] The lactone-modified product is preferably a compound in which 1 to 15 moles of lactone are added to 1 mole of a compound having a plurality of polymerizable unsaturated groups such as those shown in the examples of component (C) above, more preferably a compound in which 2 to 10 moles of lactone are added, and most preferably a compound in which 2 to 8 moles of lactone are added. The reason why the above range is preferable is the same as the reason why the alkylene oxide-modified product is preferable.
[0262] The modified product may be, for example, a compound represented by the following general formula (C-1).
[0263] [ka]
[0264] In formula (C-1), V is independently an alkylene oxide group or a group having a structure in which lactone is ring-opened. a to e are independently an integer of 0 to 6, provided that at least one of a to e is an integer of 1 to 6. a to e are preferably 1 or 2. R 51 ~R 55 are preferably independently a (meth)acryloyl group or a hydroxyl group, with the proviso that R 51 ~R 55 At least two of R are (meth)acryloyl groups. 51 ~R 55 are preferably all (meth)acryloyl groups. T is a group selected from the group consisting of substituted or unsubstituted monovalent to tetravalent hydrocarbon groups, -O- and -S-, preferably substituted or unsubstituted divalent hydrocarbon groups, -O- and -S-, more preferably -O-. q is independently 0 or 1, preferably 0. r is an integer of 1 to 4, preferably 2.
[0265] Examples of the modified product represented by general formula (C-1) include ethylene oxide-modified dipentaerythritol hexaacrylate, dipentaerythritol dicaprolactone hexaacrylate, dipentaerythritol tricaprolactone hexaacrylate, dipentaerythritol hexacaprolactone hexaacrylate, dipentaerythritol polycaprolactone hexaacrylate (all manufactured by Nippon Kayaku Co., Ltd.), trimethylolpropane propylene oxide-modified triacrylate, and trimethylolpropane ethylene oxide-modified triacrylate (all manufactured by Toagosei Co., Ltd.).
[0266] Examples of the modified products other than the compound represented by general formula (C-1) include bisphenol F ethylene oxide modified diacrylate, bisphenol A ethylene oxide modified diacrylate, isocyanuric acid ethylene oxide modified di- and triacrylate, diglycerin ethylene oxide modified acrylate (all manufactured by Toagosei Co., Ltd.), and alkylene oxide modified hexa(meth)acrylate of phosphazene.
[0267] 1-4.(D) Solvent Component (D) may be any of the following: alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 3-methoxy-1-butanol, ethylene glycol monobutyl ether, 3-hydroxy-2-butanone, diacetone alcohol, etc.; terpenes such as α- or β-terpineol, ketones such as acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, cyclopentanone, N-methyl-2-pyrrolidone, etc.; aromatic hydrocarbons such as toluene, xylene, tetramethylbenzene, etc.; cellosolve, methyl cellosolve, ethyl cellosolve, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, etc. Examples of the solvent include glycol ethers such as propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether, and esters such as ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate, 3-methoxy-3-methyl-1-butyl acetate, cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate. By dissolving and mixing using these, a uniform solution-like composition can be obtained. The amount of the solvent varies depending on the target viscosity, but it is preferable that the amount of the solvent is 50 to 90% by mass of the total mass of the adhesive layer-forming composition in order to provide appropriate coating suitability.
[0268] These solvents may be used alone or in combination of two or more to obtain the required properties such as coatability. However, in order to dissolve a large amount of component (B) in a short period of time, it is preferable to use a ketone-based solvent, more preferably acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, or cyclohexanone, and even more preferably to use cyclohexanone.
[0269] The content of the ketone-based solvent is preferably 10% by mass to 80% by mass, and more preferably 20% by mass to 70% by mass, of the total mass of the component (D). If it is 10% by mass or more, the component (B) can be easily dissolved, and if it is 80% by mass or less, the solvent residue during the coating and drying steps can be suppressed. Note that the preferred content when cyclohexanone is used as the ketone-based solvent is in the same range as above.
[0270] The content of the ketone-based solvent is preferably 5% by mass to 72% by mass, and more preferably 10% by mass to 63% by mass, based on the total mass of the composition for forming an adhesive layer. If it is 5% by mass or more, the component (B) can be easily dissolved, and if it is 72% by mass or less, the solvent can be prevented from remaining in the coating and drying steps. Note that the preferred content when cyclohexanone is used as the ketone-based solvent is in the same range as above.
[0271] 1-5.Other additives The adhesive layer-forming composition according to the present embodiment may contain additives such as photopolymerization initiators, photosensitizers, curing agents, curing accelerators, thermal polymerization inhibitors and antioxidants, plasticizers, fillers, leveling agents, defoamers, surfactants, coupling agents, etc., as necessary. In addition, the adhesive layer-forming composition may contain ultraviolet absorbers and pigments for increasing the absorbency of irradiated light.
[0272] 1-5-1. Photopolymerization initiator A photopolymerization initiator is a compound that generates active species such as radicals, cations, and anions upon stimulation with light, and initiates a polymerization reaction. Photopolymerization initiators that generate radicals upon irradiation with light are preferred.
[0273] When the adhesive layer is exposed and developed to form a pattern, it is preferable that the adhesive layer-forming composition contains a photopolymerization initiator. The active species generated from the photopolymerization initiator causes the polymerizable unsaturated groups of the (A) component and the (C) component to react with each other. This causes a difference in solubility in an alkaline developer or the like between the exposed and unexposed areas, making it possible to pattern the adhesive layer.
[0274] Examples of the photopolymerization initiator include an oxime ester initiator, an α-hydroxyacetophenone initiator, an α-aminoacetophenone initiator, an acylphosphine oxide initiator, and an intramolecular hydrogen abstraction type photopolymerization initiator. Among them, from the viewpoint of shortening the curing time of the curable composition, an oxime ester initiator or an α-aminoacetophenone initiator is preferable, and an α-aminoacetophenone initiator is more preferable. As the photopolymerization initiator, a commercially available product can be used.
[0275] Further, examples of the photopolymerization initiator include the polymerization initiators described in paragraphs 0031 to 0042 of JP-A No. 2011-095716 and paragraphs 0064 to 0081 of JP-A No. 2015-014783.
[0276] Examples of aminoacetophenone initiators include 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad379EG, the Omnirad series is a product of IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad 907), and APi-307 (1-(biphenyl-4-yl)-2-methyl-2-morpholinopropan-1-one, manufactured by Shenzhen UV-ChemTech Ltd.).
[0277] Examples of the oxime ester-based initiator include O-oxime ester-based photopolymerization initiators represented by general formula (E-1) or general formula (E-2).
[0278] [ka]
[0279] In formula (E-1), R 61 , R 62 each independently represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, or a heterocyclic group having 4 to 12 carbon atoms; R 63 represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. Here, the alkyl group and the aryl group may be substituted with an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkanoyl group having 1 to 10 carbon atoms, or a halogen, and the alkylene portion may contain an unsaturated bond, an ether bond, a thioether bond, or an ester bond. The alkyl group may be any of linear, branched, and cyclic alkyl groups.
[0280] [ka]
[0281] In formula (E-2), R 64 and R 65 R are each independently a linear or branched alkyl group having 1 to 10 carbon atoms, a cycloalkyl group, a cycloalkylalkyl group, or an alkylcycloalkyl group having 4 to 10 carbon atoms, or a phenyl group which may be substituted with an alkyl group having 1 to 6 carbon atoms. 66 are each independently a linear or branched alkyl or alkenyl group having 2 to 10 carbon atoms, and some of the -CH2- groups in the alkyl or alkenyl group may be substituted with -O- groups. 64 ~R 66 A part of the hydrogen atoms in the group may be substituted with halogen atoms.
[0282] Commercially available oxime ester initiators include, for example, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyloxime)] (trade name: IRGACURE OXE-01, IRGACURE series, manufactured by BASF), ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime) (trade name: IRGACURE OXE-02, manufactured by BASF), [8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) (trade name: IRGACURE OXE-03, manufactured by BASF), and OXE-03, manufactured by BASF), 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methylpentanone-1-(O-acetyloxime) (trade name: IRGACURE OXE-04, manufactured by BASF, and trade name: Lunar 6, DKSH Japan), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-305, Changzhou Strong Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazol-3-yl]-, 2-(O-acetyloxime) (trade name: TR-PBG-326, Changzhou Strong Electronic New Materials Co., Ltd.), and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-391, Changzhou Strong Electronic New Materials Co., Ltd.).
[0283] Other photopolymerization initiators include, for example, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one (trade name: Omnirad 127), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad 369), 2-hydroxy-2-methyl-1-phenyl-propan-1-one (trade name: Omnirad 1173), 1-hydroxy-cyclohexyl-phenyl-ketone (trade name: Omnirad 184), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819).
[0284] The adhesive layer-forming composition preferably contains the photopolymerization initiator in an amount of 0.1% by mass to 30% by mass, more preferably 0.3% by mass to 20% by mass, based on the total mass of the component (A). When the photopolymerization initiator content is 0.1% by mass, photopolymerization can be promoted and the photopolymerization rate can be increased. When the photopolymerization initiator content is 30% by mass or less, excessive increase in sensitivity can be suppressed, and scorching, peeling residue, and the like can be prevented from occurring when ablation is performed by irradiating light.
[0285] 1-5-2. Photosensitizers Examples of the photosensitizer include acetophenones such as triethanolamine, triisopropanolamine, benzophenone, 4,4'-bisdimethylaminobenzophenone (Michler's ketone), 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4,4'-diethylaminobenzophenone, acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminopropiophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; benzoin ethers such as benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; 2-dimethylaminoethylbenzoic acid, 4-dimethylaminobenzoic acid ethyl, 4-dimethylaminobenzoic acid (n-butoxy) ether, and the like. benzophenones such as ethyl, 4-dimethylaminobenzoate isoamyl, 4-dimethylaminobenzoate 2-ethylhexyl, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthones such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; aminobenzophenones such as 4,4'-bisdiethylaminobenzophenone; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, and camphorquinone.
[0286] In the curable composition, the content of the photosensitizer is preferably 0.5% by mass to 400% by mass, more preferably 1% by mass to 300% by mass, based on the total mass of the photopolymerization initiator. When the content of the photosensitizer is 0.5% by mass or more, the sensitivity of the photopolymerization initiator can be improved, and the photopolymerization rate can be increased. When the content of the photosensitizer is 400% by mass or less, an excessive increase in sensitivity can be suppressed, and scorching, peeling residue, and the like can be prevented from occurring when ablation is performed by irradiating light.
[0287] 1-5-3.Other Examples of curing agents include amine compounds, polyvalent carboxylic acid compounds, phenolic resins, amino resins, dicyandiamide, Lewis acid complex compounds, etc., which contribute to the curing of epoxy resins. Examples of curing accelerators include tertiary amines, quaternary ammonium salts, tertiary phosphines, quaternary phosphonium salts, boric acid esters, Lewis acids, organometallic compounds, imidazoles, etc., which contribute to the curing acceleration of epoxy resins. Examples of thermal polymerization inhibitors and antioxidants include hydroquinone, hydroquinone monomethyl ether, pyrogallol, tert-butylcatechol, phenothiazine, hindered phenol compounds, etc. Examples of plasticizers include dibutyl phthalate, dioctyl phthalate, tricresyl phosphate, etc. Examples of fillers include glass fiber, silica, mica, alumina, etc. Examples of defoamers and leveling agents include silicone-based, fluorine-based, and acrylic compounds. Examples of surfactants include fluorine-based surfactants, silicone-based surfactants, etc. Examples of coupling agents include 3-(glycidyloxy)propyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-ureidopropyltriethoxysilane, and the like.
[0288] 2.Laminate The laminate according to this embodiment includes a support, an adherend, and an adhesive layer including a coating or cured film of the above-mentioned adhesive layer forming composition disposed between the support and the adherend.
[0289] The laminate according to this embodiment can also be suitably used as a substrate for patterning using a resist material, and a resist layer or a material layer may be disposed on the side of the adherend opposite the side in contact with the adhesive layer.
[0290] Here, the material layer is not particularly limited as long as it is a layer that can be patterned using a resist material. The material layer includes metal films and semiconductor films used in semiconductor elements, wiring, terminals, etc. included in electronic devices. The material layer may be a patterned layer or an unpatterned layer. When the material layer is composed of two or more layers, all layers may be unpatterned layers, some layers may be patterned and the rest may be unpatterned layers, or all layers may be patterned layers.
[0291] For example, when the material layer is patterned by an etching process, the resist layer may be disposed so as to sandwich the material layer between the resist layer and the adherend. In this case, the material layer preferably includes an unpatterned layer, and when the material layer is composed of two or more layers, it is preferable that at least one layer is an unpatterned layer. When simply forming a concave-convex pattern on a substrate or when patterning the material layer by a lift-off process, the resist layer may be disposed in contact with the adherend.
[0292] The laminate according to the present embodiment may also include a patterned material layer disposed on the surface of the adherend opposite to the surface on which the adhesive layer is disposed. When the material layer is composed of two or more layers, it is sufficient that at least one layer is patterned, and an unpatterned layer may also be included.
[0293] 2-1.Support There are no limitations on the type of support, so long as an adhesive layer can be formed on the surface thereof.
[0294] In this embodiment, the support is preferably laser transmissive. In particular, the support is more preferably transmissive to light (laser) having a wavelength of 10 nm to 400 nm, and even more preferably transmissive to light (laser) having a wavelength of 100 nm to 400 nm. Examples of the support having the laser transmissive property include a glass substrate, an acrylic substrate, a sapphire substrate, and a quartz substrate. However, for the glass substrate and the acrylic substrate, it is necessary to use a substrate having a composition that has a sufficient transmittance of the wavelength of the light to be used. Of the above supports, a glass substrate is preferable.
[0295] 2-2.Adherent Examples of the adherend include a semiconductor wafer, a semiconductor chip, a light-emitting element, an optical glass wafer, a metal foil, a polishing pad, a resin coating film, a wiring layer, etc. The adherend may be a single layer, or may have a multilayer structure of two or more layers, and some or all of the layers may be patterned. When used as a substrate for patterning using a resist material, the adherend preferably includes a semiconductor wafer.
[0296] In addition, the adherend may have an uneven pattern formed on the surface opposite to the surface in contact with the adhesive layer.
[0297] 2-3.Adhesive layer The adhesive layer is formed by applying the above-mentioned adhesive layer-forming composition to the surface of a support and / or an adherend, and then undergoing at least a step of drying off the solvent.
[0298] Among the adhesive layers that have been subjected to the above-mentioned solvent drying step, the one before the heat treatment under the preferred heat treatment conditions (temperature, time) for promoting the crosslinking reaction described below is also called the "coating film" of the adhesive layer-forming composition. Also, the one after the heat treatment under the preferred heat treatment conditions (temperature, time) for promoting the crosslinking reaction described below is also called the "cured film" of the adhesive layer-forming composition.
[0299] 2-4.Resist layer The components used in the resist layer may be any known material. The components used in the resist layer are not particularly limited as long as they can be patterned in the developing step described below and can be peeled off in the peeling step. The resist layer may be a positive resist layer or a negative resist layer.
[0300] Moreover, as the resist layer forming material, commercially available liquid resist layer forming materials and dry film resists can also be used.
[0301] 2-5.Material layer The material layer may be a single layer, or may have a multi-layer structure of two or more layers.
[0302] The material layer may be made of any known material, including silicon materials such as silicon oxide, silicon nitride, and silicon oxynitride, and metal materials such as metal oxide.
[0303] 3. Manufacturing method of laminate The method for producing a laminate according to this embodiment includes the steps of i) forming an adhesive layer containing the adhesive layer-forming composition on the surface of either or both of the support and the adherend, and ii) bonding the support and the adherend via the formed adhesive layer.
[0304] The method for producing the laminate may also include a step of exposing and developing the adhesive layer, and a step of applying a resist layer.
[0305] In the above-mentioned step i) of forming an adhesive layer and / or step ii) of bonding the support and the adherend, the adhesive layer is preferably heat-treated. By heat-treating the adhesive layer, the polymerizable unsaturated groups of the (A) component and the (C) component react with each other, and further the reaction between the acidic group of the (A) component and the epoxy group of the (B) component proceeds. As the reaction proceeds, a strong cross-linked structure can be formed, and the alkali resistance of the adhesive layer can be further improved.
[0306] The heat treatment may be performed before a step requiring alkali resistance, and is not limited to the step of i) forming an adhesive layer or the step of ii) bonding the support and the adherend. For example, in the case of a laminate including a resist layer, the heat treatment may be performed before the peeling step of peeling the resist layer with an alkaline stripping solution described below.
[0307] The heat treatment temperature for promoting the crosslinking reaction is preferably 150°C to 250°C, more preferably 180°C to 230°C. The heat treatment time is preferably 10 minutes to 120 minutes, more preferably 30 minutes to 90 minutes. By setting the treatment temperature at 150°C or higher and the treatment time at 10 minutes or longer, the crosslinking reaction proceeds well and the alkali resistance of the adhesive layer can be increased. By setting the treatment temperature at 250°C or lower and the treatment time at 120 minutes or shorter, unintended side reactions do not occur and coloring of the cured film and a decrease in adhesive strength can be suppressed.
[0308] Each step will be described below.
[0309] 3-1. Step of forming adhesive layer The adhesive layer forming step is a step of applying the above-mentioned adhesive layer forming composition to the surface of a support and / or an adherend to form an adhesive layer containing the above-mentioned adhesive layer forming composition.
[0310] Examples of the method for applying the adhesive layer-forming composition include known solution immersion methods, spin coating methods, inkjet methods, spray methods, and methods using a roller coater, land coater, slit coater, or spinner.
[0311] After the adhesive layer is applied by the above application method, the solvent is dried (prebaked) to form the adhesive layer. Note that prebaking is performed by heating using an oven, a hot plate, etc. The heating temperature and heating time in prebaking are appropriately selected depending on the solvent used, and for example, prebaking is performed at a temperature of 60 to 110°C for 1 to 3 minutes.
[0312] The thickness of the adhesive layer can be selected arbitrarily. In this embodiment, the thickness of the adhesive layer is preferably 0.1 μm to 50 μm, and more preferably 0.5 μm to 30 μm. When the thickness of the adhesive layer is 0.1 μm or more, the adhesive layer can have sufficient holding power to adhere to the adherend. Also, when the thickness is 50 μm or less, the adhesive layer can be sufficiently cured by light or heat curing.
[0313] 3-2. Exposure and development process of adhesive layer In addition, this process may include an exposure process and a development process for forming a pattern in the adhesive layer after applying the adhesive layer to the surface of either one or both of the above-mentioned support and the above-mentioned adherend. By patterning the adhesive layer, the adhesive layer can be formed only in the portion where the adherend is to be adhered, and in the process of separating the support and the adherend (described later), peeling failure and positional deviation of the adherend can be suppressed.
[0314] Examples of light used in the exposure step include visible light, ultraviolet light, far ultraviolet light, electron beams, X-rays, and the like. Among the above-mentioned light, ultraviolet light (wavelength 250 to 400 nm) is preferred. In addition, in the development step, a developer suitable for alkaline development is used. Examples of the developer include aqueous solutions of sodium carbonate, potassium carbonate, potassium hydroxide, diethanolamine, tetramethylammonium hydroxide, and the like. These developers can be appropriately selected according to the characteristics of the resin layer, and a surfactant may be added as necessary. The development temperature is preferably 20 to 35°C, and fine images can be precisely formed using a commercially available developing machine, ultrasonic cleaner, or the like. After the alkaline development, the film is usually washed with water. As the development treatment method, a shower development method, a spray development method, a dip (immersion) development method, a puddle (liquid puddle) development method, and the like can be applied.
[0315] 3-3. Step of bonding the support and the adherend The step of adhering the support and the adherend is a step of adhering the support and the adherend via the adhesive layer.
[0316] As a method for bonding the support and the adherend, for example, there is a method of contacting the adherend (wherein the adhesive is applied to the surface that contacts the adhesive layer) with the surface of the adhesive layer formed on the surface of the support and pressurizing the adherend while heating it. In addition, as for the bonding conditions between the support and the adherend, the temperature during pressurization is preferably from room temperature to 200°C or less, more preferably from 30°C to 150°C. The pressure during bonding is preferably from 0.01MPa to 20MPa, more preferably from 0.03MPa to 15MPa. In addition, if necessary, after completion of the pressurized thermocompression bonding, the bond can be thermally cured at a temperature of 120°C to 250°C. By bonding the support and the adherend under the above conditions, the adherend is more firmly fixed to the surface of the support via the adhesive layer.
[0317] In the bonding step, the support and the adherend may be bonded by photocuring. An example of a method for photocuring the adhesive layer is a method of irradiating light using a high-pressure mercury lamp. The bonding conditions for the support and the adherend are preferably such that the wavelength of the irradiated light is 200 to 500 nm. The exposure dose of the irradiated light is 25 mJ / cm. 2 ~3000mJ / cm 2 and preferably 50 mJ / cm 2 ~2000mJ / cm 2 It is more preferable that:
[0318] In this manner, the laminate of the present embodiment is formed.
[0319] The laminate can be separated into the support and the adherend by irradiating the adhesive layer from the support side with a laser having a wavelength of 10 nm to 400 nm, as described below.
[0320] 3-4. Step of applying resist layer The resist layer can be applied by a known method. Examples of the resist layer application method include a solution immersion method, a spin coating method, an inkjet method, a spray method, a screen printing method, a curtain coating method, a method using a roller coater, a land coater, a slit coater, or a spinner. In addition, when a dry film resist is used, the application may be performed by laminating a dry film.
[0321] The resist layer may be applied before the step of i) forming the adhesive layer, or before the step of ii) bonding the support and the adherend, or after the step of ii) bonding the support and the adherend. When the resist layer has thermosetting properties, it is preferable that the resist layer is applied after the step of heat-treating the adhesive layer. By applying the resist layer after the step of heat-treating the adhesive layer, the developability in the developing step of the resist layer described below can be improved.
[0322] 4. Method for manufacturing a laminate including a patterned material layer A method for manufacturing a laminate including a patterned material layer (hereinafter also referred to as "patterned material") includes: (i) a preparation step of preparing a laminate including an unexposed resist layer; (ii) an exposure step of irradiating a part of the resist layer with radiation through a photomask; (iii) a development step of developing the resist layer irradiated with radiation and removing the resist layer in the exposed or unexposed portion; and (iv) a stripping step of stripping the resist layer with an alkaline stripping solution.
[0323] In addition, a laminate provided with an adhesive layer may be prepared in the preparation step (a), or the adhesive layer may be provided after the steps (b) to (d). From the viewpoint of improving the stability of transporting the substrate in the exposure step (b), the development step (c), and the peeling step (d), it is preferable to prepare a laminate provided with an adhesive layer in the preparation step (a).
[0324] The patterned material refers to a material layer that is patterned. For example, a material layer is formed before any of the above steps A) to D), and the material layer is patterned by an etching process or a lift-off process to obtain a patterned material.
[0325] For example, when the material layer is patterned by an etching process, the material layer is preferably formed before the preparation step (a). When the material layer is patterned by a lift-off process, the material layer is preferably formed before the peeling step (d).
[0326] The material layer can be applied by a known method, examples of which include a vapor deposition method, a sputtering method, a molecular lamination method, a coating method, an inkjet method, and a printing method.
[0327] When the material layer is patterned by an etching process, a known method can be used for the etching process. Examples of the etching process include plasma etching, ion etching, reactive ion etching, and sputter etching. Also, a known device can be used for dry etching. Examples of gases that can be used for dry etching include fluorine-based gases such as CHF3, CF4, C2F6, C3F8, and SF6, chlorine-based gases such as Cl2 and BCl3, oxygen-based gases such as O2 and O3, reducing gases such as H2, NH3, CO, CO2, CH4, C2H2, C2H4, C2H6, C3H4, C3H6, C3H8, HF, HI, HBr, HCl, NO, NH3, and BCl3, and inert gases such as He, N2, and Ar. These gases can be used in a mixture.
[0328] 4-1. Preparation step of preparing a laminate including an unexposed resist layer The step of preparing a laminate including an unexposed resist layer is a step of obtaining a laminate including a resist layer by the above-mentioned method, or of preparing a laminate to which an unexposed resist layer has already been applied.
[0329] 4-2. Exposure process in which part of the resist layer is irradiated with radiation through a photomask The exposure step is a step of irradiating a part of the resist layer with radiation through a photomask, thereby causing a part of the etching resist layer to photoreact.
[0330] The photomask may be a known one. Examples of the photomask include multi-tone masks such as halftone masks and graytone masks. In the graytone mask, a light-shielding portion and a diffraction grating are formed on a light-transmitting substrate. In the diffraction grating, the spacing between light-transmitting regions such as slits, dots, and meshes is equal to or less than the resolution limit of the light used for exposure, and this configuration controls the light transmittance. In the halftone mask, a light-shielding portion and a semi-transmitting portion are formed on a light-transmitting substrate. The semi-transmitting portion controls the transmittance of the light used for exposure.
[0331] Examples of the radiation to be irradiated include visible light, ultraviolet light, far ultraviolet light, electron beams, and X-rays. Of the above-mentioned radiation, ultraviolet light is preferable. Furthermore, a known exposure device (ultra-high pressure mercury lamp, high pressure mercury lamp, metal halide lamp, far ultraviolet lamp, etc.) can be used as a device for irradiating radiation. Furthermore, the wavelength of the irradiated radiation is preferably 250 nm to 400 nm. The exposure dose of the radiation is 25 mJ / cm. 2 ~3000mJ / cm 2 and preferably 50 mJ / cm 2 ~2000mJ / cm 2 It is more preferable that:
[0332] 4-3. A development step in which the resist layer is developed and the exposed or unexposed portions of the resist layer are removed. The developing step is a step of developing the resist layer irradiated with radiation. When the resist layer is a positive type, the exposed portion is removed, and when the resist layer is a negative type, the unexposed portion is removed. The developing method may be appropriately selected from known methods according to the type of resist layer.
[0333] Examples of the developing method of the resist layer include shower developing method, spray developing method, dip (immersion) developing method, puddle (liquid puddle) developing method, etc. The developing method can be performed using a commercially available developing machine, ultrasonic cleaner, etc.
[0334] In addition, when performing alkaline development, examples of the alkaline developer include aqueous solutions of alkali (basic compounds) such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, lithium carbonate, sodium silicate, sodium metasilicate, ammonia, ethylamine, n-propylamine, diethylamine, diethylaminoethanol, di-n-propylamine, triethylamine, methyldiethylamine, dimethylethanolamine, triethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, pyrrole, piperidine, 1,8-diazabicyclo[5.4.0]-7-undecene, and 1,5-diazabicyclo[4.3.0]-5-nonane. The method of alkaline development may be appropriately selected from known methods according to the type of etching resist.
[0335] 4-4. Stripping process to strip the resist layer with an alkaline stripper The resist layer is stripped off from the laminate using an alkaline stripper.
[0336] In the peeling step, it is sufficient to peel off at least the resist layer. For example, when the resist layer is peeled off by an etching process, it is preferable that the resist layer is peeled off from the material layer. In addition, when the adherend is patterned or the resist layer is removed by a lift-off process, it is preferable that the resist layer is peeled off from the adherend.
[0337] A known alkaline stripper can be used. As such a stripper, for example, an alkaline stripper containing sodium hydroxide can be used. When developing using an alkaline developer, the alkaline stripper is more alkaline than the alkaline developer used in the development process, and can strip the resist layer that was not removed by the developer. When using an aqueous sodium hydroxide solution as the alkaline stripper, it is preferable to use a solution of 5% by mass to 20% by mass. The temperature of the alkaline stripper in the stripping process is preferably 40° C. to 80° C. The contact time of the alkaline stripper is preferably 5 minutes to 60 minutes. By setting the concentration, temperature, and contact time of the alkaline stripper to the above ranges, the resist layer can be stripped well.
[0338] In this manner, a laminate including the patterned material according to this embodiment is formed.
[0339] The above laminate can also be separated into the support and the adherend by irradiating the adhesive layer from the support side with a laser having a wavelength of 10 nm to 400 nm, as described below.
[0340] 5. Processing method of laminate The method for treating a laminate according to this embodiment includes the steps of (1) preparing the laminate described above, and (2) irradiating the laminate with light to separate the support and the adherend. Each step will be described below. Note that the steps (1) and (2) may be performed continuously, or step (2) may be performed after a certain time has elapsed since step (1).
[0341] This laminate can be used to transport a plurality of adherends held by a support. As described above, the adherend may be a single layer, or may be a multilayer of two or more layers. In addition, the laminate may have a resist layer or a material layer disposed on the surface of the adherend opposite to the surface in contact with the adhesive layer, and the adherend, resist layer, and material layer may each be patterned or unpatterned.
[0342] 5-1. Step of preparing laminate The step of preparing a laminate is a step of forming a laminate as described above, or of preparing an already formed laminate.
[0343] 5-2. Step of separating the support and the adherend The step of separating the support and the adherend is a step of separating the support and the adherend by irradiating the adhesive layer with light.
[0344] The light to be irradiated is not particularly limited as long as it can separate the support and the adherend. In this embodiment, the light is preferably ultraviolet light, and the wavelength of the ultraviolet light is more preferably 10 nm to 400 nm, and even more preferably 100 nm to 400 nm. If the wavelength of the ultraviolet light is 10 nm or more, the polymer, which is a component of the adhesive layer, absorbs the light and changes its quality, reducing the strength and adhesive force, so that the support and the adherend can be easily separated. In addition, if the wavelength is 400 nm or less, the adhesive layer in the processed portion absorbs the light, so that the generation of residue of the cured film can be suppressed.
[0345] Examples of the ultraviolet light source include a low mercury lamp, a high pressure mercury lamp, an extra-high pressure mercury lamp, a metal halide lamp, a far ultraviolet light laser, etc. Among the above light sources, a laser is preferable.
[0346] Examples of the laser include solid-state lasers, liquid lasers, and gas lasers. Examples of the solid-state laser include semiconductor pumped lasers. Examples of the liquid laser include dye lasers. Examples of the gas laser include excimer lasers. Among the lasers, semiconductor pumped lasers are preferred.
[0347] Examples of the semiconductor pumped laser include Nd:YAG laser, Nd:YLF laser, Nd:glass laser, Nd:YVO4 laser, Yb:YAG laser, Yb-doped fiber laser, Er:YAG laser, Tm:YAG laser, etc. Examples of the excimer laser include KrF laser, XeCl laser, ArF laser, F2 laser, etc. Among the above lasers, the Nd:YAG laser is preferred.
[0348] The output and cumulative light quantity of the light irradiated onto the adhesive layer vary depending on the type of light source, etc., but when the irradiated light is a laser, the output can be 0.1 mW to 200 W. The cumulative light quantity can be 1 mJ / cm2. 2 ~50J / cm 2 It is preferable that the integrated light amount is 0.1 mJ / cm 2 If the intensity is more than 50 J / cm, burning and peeling residue are less likely to occur during ablation. 2 If the ablation speed is equal to or less than this, the ablation speed can be appropriately controlled to perform appropriate processing.
[0349] As a method of irradiating the adhesive layer with light (laser), it is preferable to irradiate the entire surface of the adhesive layer with a laser from the support side. The method of irradiating the laser is not particularly limited, and can be performed by a known method.
[0350] The laminate is capable of separating the support and the adherend by irradiating the adhesive layer with light (laser).
[0351] The method for treating a laminate according to this embodiment may include a step of processing the prepared laminate prior to the step of separating the support and the adherend.
[0352] Methods for processing the laminate include thinning of adherends such as dicing and back grinding, photofabrication, stacking of semiconductor chips, mounting of various elements, resin sealing, and the like.
[0353] The method for treating a laminate according to the present embodiment may further include a step of transferring the processed laminate from one device to another. A method for transferring the laminate includes using a robot arm or the like.
[0354] In this manner, the laminate of this embodiment is processed. EXAMPLES
[0355] Hereinafter, the embodiments of the present invention will be described in detail based on examples and comparative examples, but the present invention is not limited to these.
[0356] First, synthesis examples of the unsaturated group-containing polymerizable resin, component (A), will be described. Unless otherwise specified, the resins in these synthesis examples were evaluated as follows.
[0357] In addition, when the same model of measuring equipment is used, the name of the equipment manufacturer is omitted from the second place. In addition, in the examples, all glass substrates used to prepare the substrates with cured films for measurement are used after the same treatment. In addition, when the first decimal place of the content of each component is 0, the notation after the decimal point may be omitted.
[0358] [Solid content concentration] 1 g of the resin solution obtained in Synthesis Example was impregnated into a glass filter (weight: W0(g)), weighed [W1(g)], and the weight after heating at 160°C for 2 hours [W2(g)] was calculated from the following formula. Solid content concentration (weight%) = 100 × (W2-W0) / (W1-W0)
[0359] [Acid value] The resin solution was dissolved in dioxane and titrated with a 1 / 10N KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.) to determine the content.
[0360] [Molecular weight] Measurement was performed using gel permeation chromatography (GPC) "HLC-8220GPC" (manufactured by Tosoh Corporation, solvent: tetrahydrofuran, columns: TSKgelSuper H-2000 (2 columns) + TSKgelSuper H-3000 (1 column) + TSKgelSuper H-4000 (1 column) + TSKgelSuper H-5000 (1 column) (manufactured by Tosoh Corporation), temperature: 40°C, rate: 0.6 ml / min), and the weight average molecular weight (Mw) was calculated as a value converted into standard polystyrene (manufactured by Tosoh Corporation, PS-oligomer kit).
[0361] [Absorbance of component (A) at 260 nm to 400 nm] The absorbance can be determined by measuring the absorbance of a 0.001 wt % PGMEA solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation).
[0362] [Absorbance of component (B) at 266 nm] The absorbance can be determined by measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using a UV-Vis-Infrared Spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation).
[0363] The abbreviations used in the Synthesis Examples are as follows. BPFE: Bisphenol fluorene type epoxy resin (epoxy resin with general formula (5) where Ar is a benzene ring and l is 0, epoxy equivalent 256g / eq) AA: Acrylic acid TPP: Triphenylphosphine PGMEA: Propylene glycol monomethyl ether acetate BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride THPA: 1,2,3,6-Tetrahydrophthalic anhydride RUVA-93: 2-(2'-hydroxy-5'-methacryloyloxyethyl phenyl) Nyl)-2-H-benzotriazole (Otsuka Chemical Co., Ltd.) MMA: Methyl methacrylate MA: methacrylic acid HEMA: 2-hydroxyethyl methacrylate ADVN: 2,2'-azobis(2,4-dimethylvaleronitrile) MOI: 2-isocyanatoethyl methacrylate DCPMA: dicyclopentanyl methacrylate GMA: Glycidyl methacrylate St: styrene AIBN: Azobisisobutyronitrile TDMAMP: Trisdimethylaminomethylphenol HQ: Hydroquinone SA: Succinic anhydride TEA: Triethylamine
[0364] [Synthesis Example 1] In a 250 mL four-neck flask equipped with a reflux condenser, BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were charged and stirred at 100 to 105° C. for 12 hours to obtain a reaction product. Thereafter, PGMEA (25.00 g) was added to the reaction product, and the solid content was adjusted to 50.0 mass%.
[0365] Next, BPDA (14.37 g, 0.05 mol) and THPA (7.43 g, 0.05 mol) were added to the obtained reaction product, and the mixture was stirred at 115 to 120 ° C for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-1. The solid content concentration of the obtained resin solution was 57.0 mass%, the acid value (solid content equivalent) was 96 mg KOH / g, and the Mw by GPC analysis was 3600. In addition, the maximum absorbance at 260 nm to 400 nm was 0.22 (275 nm).
[0366] [Synthesis Example 2] In a 250 mL four-neck flask equipped with a reflux condenser, BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were charged and stirred at 100 to 105° C. for 12 hours to obtain a reaction product. Thereafter, PGMEA (25.00 g) was added to the reaction product, and the solid content was adjusted to 50.0 mass%.
[0367] Next, BPDA (10.06 g, 0.03 mol) and THPA (11.89 g, 0.08 mol) were added to the obtained reaction product, and the mixture was stirred at 115 to 120 ° C for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-2. The solid content concentration of the obtained resin solution was 57.0 mass%, the acid value (solid content equivalent) was 98 mg KOH / g, and the Mw by GPC analysis was 2300. In addition, the maximum absorbance at 260 nm to 400 nm was 0.20 (275 nm).
[0368] [Synthesis Example 3] In a 250 mL four-neck flask equipped with a reflux condenser, BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were charged and stirred at 100 to 105° C. for 12 hours to obtain a reaction product. Thereafter, PGMEA (25.00 g) was added to the reaction product, and the solid content was adjusted to 50.0 mass%.
[0369] Next, BPDA (19.25 g, 0.07 mol) and THPA (0.30 g, 0.002 mol) were added to the obtained reaction product, and the mixture was stirred at 115 to 120 ° C for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-3. The solid content concentration of the obtained resin solution was 56.3 mass%, the acid value (solid content equivalent) was 97 mg KOH / g, and the Mw by GPC analysis was 4700. In addition, the maximum absorbance at 260 nm to 400 nm was 0.23 (275 nm).
[0370] [Synthesis Example 4] In a reactor equipped with a temperature controller, stirrer, reflux condenser, and nitrogen gas inlet tube, PGMEA (233 parts by weight) as a solvent, RUVA-93 (59 parts by weight, 0.18 mol) as an unsaturated monomer containing a UV-absorbing group, MMA (16 parts by weight, 0.16 mol), MA (9.0 parts by weight, 0.10 mol), and HEMA (15 parts by weight, 0.12 mol) as other unsaturated monomers were added and heated to 80°C, and then replaced with nitrogen. ADVN (2 parts by weight) was added as a polymerization initiator and reacted for 1 hour. Then, ADVN (0.5 parts by weight) was added and heated to 90°C and aged for 3 hours to synthesize a UV-absorbing copolymer. The molar absorption coefficient of RUVA-93 at a wavelength of 355 nm was 17,000 L / (mol·cm). The molar absorption coefficient can be calculated by measuring the absorbance of a 0.001 wt% acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation), and then dividing the absorbance by the molar concentration.
[0371] To this, MOI (18 parts by weight, 0.12 mol), a tin compound (0.01 parts by weight) as a catalyst, and methoquinone (0.04 parts by weight) as a polymerization inhibitor were added, and the MOI addition reaction to the ultraviolet absorbing copolymer was carried out at 60°C for about 6 hours. The end point of the reaction was confirmed by the disappearance of the isocyanate peak from FT-IR. After the reaction was completed, PGMEA was added to this to adjust the solid content to 30.0% by weight, and an unsaturated group-containing alkali-soluble resin (A)-4 was obtained. The acid value (solid content equivalent) of the obtained resin solution was 55 mgKOH / g, and Mw by GPC analysis was 30,000. The maximum absorbance at 260 nm to 400 nm was 0.25 (334 nm).
[0372] [Synthesis Example 5] PGMEA (300 g) was placed in a 1 L four-neck flask equipped with a reflux condenser, and the flask was purged with nitrogen and then heated to 120° C. A mixture of AIBN (10 g) dissolved in a monomer mixture (DCPMA (77.1 g, 0.35 mol), GMA (49.8 g, 0.35 mol), St (31.2 g, 0.30 mol)) was added dropwise from a dropping funnel to the flask over 2 hours, and the mixture was stirred at 120° C. for another 2 hours to obtain a copolymer solution.
[0373] Next, after replacing the inside of the flask system with air, AA (24.0 g, 95% of glycidyl group), TDMAMP (0.8 g) and HQ (0.15 g) were added to the obtained copolymer solution and stirred at 120 ° C for 6 hours to obtain a polymerizable unsaturated group-containing copolymer solution. SA (30.0 g, 90% of the moles of AA added) and TEA (0.5 g) were added to the obtained polymerizable unsaturated group-containing copolymer solution and reacted at 120 ° C for 4 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-5. The solid content concentration of the resin solution was 46.0 mass%, the acid value (solid content equivalent) was 76 mg KOH / g, and Mw by GPC analysis was 5300. In addition, the maximum absorbance at 260 nm to 400 nm was 0.05 (270 nm).
[0374] A composition for forming an adhesive layer was prepared in the blend amounts (unit: mass %) shown in Tables 1 and 2. The blend components used in Tables 1 and 2 are as follows.
[0375] (Alkali-soluble resin containing unsaturated groups) (A)-1: Resin solution obtained in Synthesis Example 1 (solid content concentration: 57.0% by mass) (A)-2: Resin solution obtained in Synthesis Example 2 (solid content concentration: 57.0% by mass) (A)-3: Resin solution obtained in Synthesis Example 3 (solid content concentration: 56.3% by mass) (A)-4: Resin solution obtained in Synthesis Example 4 (solid content concentration: 30.0% by mass) (A)-5: Resin solution obtained in Synthesis Example 5 (solid content concentration: 46.0% by mass)
[0376] (Epoxy compounds) (B)-1: Biphenyl-type epoxy resin (jER YX4000, manufactured by Mitsubishi Chemical Corporation; "jER" is a registered trademark of the company; epoxy equivalent: 190 g / eq) (B)-2: Bisphenol A type epoxy resin (jER 828, manufactured by Mitsubishi Chemical Corporation, "jER" is a registered trademark of the company, epoxy equivalent 185g / eq) (B)-3: Bisphenol fluorene diglycidyl ether (epoxy equivalent: 256 g / eq) (B)-4: 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (EHPE3150, Daicel Corporation, epoxy equivalent 180g / eq) (B)-5: Trimethylolpropane triglycidyl ether (Epolite 100MF, Kyoeisha Chemical Co., Ltd., epoxy equivalent 140 g / eq) (B)-6: Showfree BATG (manufactured by Resonac Corporation, "Showfree" is a registered trademark of the company, epoxy equivalent 120g / eq)
[0377] (polymerizable compound) (C)-1: Mixture of dipentaerythritol pentaacrylate and hexaacrylate (DPHA, manufactured by Nippon Kayaku Co., Ltd.) (C)-2: Trimethylolpropane triacrylate with 6 moles of ethylene oxide (Aronix M-360, manufactured by Toagosei Co., Ltd.)
[0378] (solvent) (D)-1: Propylene glycol monomethyl ether acetate (PGMEA) (D)-2: Cyclohexanone (ANON)
[0379] [Table 1] In the table, "(B) / (A)" indicates the ratio of the total mass of component (B) contained in the composition for forming an adhesive layer to the total mass of component (A), and "(C) / [(A)+(B)]" indicates the ratio of the total mass of component (C) contained in the composition for forming an adhesive layer to the combined mass of components (A) and (B).
[0380] [Table 2] In the table, "(B) / (A)" indicates the ratio of the total mass of component (B) contained in the composition for forming an adhesive layer to the total mass of component (A), and "(C) / [(A)+(B)]" indicates the ratio of the total mass of component (C) contained in the composition for forming an adhesive layer to the combined mass of components (A) and (B).
[0381] [evaluation] The compositions for forming an adhesive layer shown in Tables 1 and 2 were evaluated as follows.
[0382] [Laser processability (peelability) evaluation] (Preparation of substrate for evaluation of laser processability (peelability)) The adhesive layer-forming compositions shown in Tables 1 and 2 were applied onto a glass substrate "#1737" using a spin coater so that the film thickness after drying would be 1.0 μm, and a coating film was produced by pre-baking using a hot plate at 100° C. for 5 minutes. Next, the coating film was main-cured (post-baked) at 230° C. for 30 minutes using a hot air dryer to obtain substrates with cured films according to Examples 1 to 15 and Comparative Examples 1 to 5.
[0383] (Evaluation method) After the main curing (post-baking), the cured film was irradiated with a laser (laser wavelength: 266 nm) using a flash lamp pumped Nd:YAG Q-SW laser oscillator "Callisto" (manufactured by V Technology Co., Ltd.). The cured film was processed (removed) with a laser energy of 3 to 550 mJ / cm2, and the amount of film loss in the laser irradiated area was measured with a non-contact three-dimensional optical interference microscope "WYKO Contour-GT" (manufactured by Bruker Japan). Evaluation was based on the laser irradiation amount required to achieve a film loss of 0.1 μm, according to the following criteria. A score of △ or higher was considered to be acceptable.
[0384] (Evaluation Criteria) ◎: 100mJ / cm 2 Below this, the amount of film reduction is 0.1μm. ○: 100mJ / cm 2 Super 150mJ / cm 2 Below this, the amount of film reduction is 0.1μm. △: 150mJ / cm 2 Super 200mJ / cm 2 Below this, the amount of film reduction is 0.1μm. ×:200mJ / cm 2 The reduction in the cured film is less than 0.1μm.
[0385] (Preparation of substrate with cured film for evaluating alkali resistance) The adhesive layer-forming compositions shown in Tables 1 and 2 were applied onto a glass substrate "#1737" using a spin coater so that the film thickness after heat curing treatment would be 4.0 μm, and a coating film was produced by pre-baking using a hot plate at 100° C. for 5 minutes. Next, the coating film was main-cured (post-baked) at 230° C. for 30 minutes using a hot air dryer, and substrates with cured films according to Examples 1 to 15 and Comparative Examples 1 to 5 were obtained.
[0386] [Alkaline resistance evaluation] (Evaluation method) The cured film on the obtained substrate with the cured film was immersed in an 8.7% by mass aqueous solution of sodium hydroxide at 70°C for 10 minutes, washed with pure water, and dried. The thickness of the cured film after the test was then measured using a stylus-type step shape measuring device "P-17" (manufactured by KLA-Tencor Corporation). A grade of △ or higher was deemed to be a pass.
[0387] The remaining film rate in the alkali resistance evaluation was calculated from the following formula, where the film thickness before the test was L1 and the film thickness after the test was L2. Remaining film rate (%)=L2 / L1×100
[0388] (Evaluation Criteria) ◎: Remaining film rate is 95% or more ○: Residual film rate is 90% or more △: Residual film rate is 80% or more and less than 90% ×: Residual film rate is less than 80%
[0389] (Preparation of substrate for shear strength (adhesive strength) evaluation) The adhesive layer compositions shown in Tables 1 and 2 were applied onto a glass substrate "#1737" using a spin coater so that the film thickness after heat curing treatment would be 4.0 μm, and the film was pre-baked using a hot plate at 100° C. for 5 minutes to produce a dry film.
[0390] Next, a glass substrate "#1737" cut to 2 mm x 2 mm was placed on the pattern and pressure-bonded at 110°C for 1 minute while applying a pressure of 0.3 MPa. Thereafter, the substrate was post-cured (post-baked) for 30 minutes at 230°C using a hot air dryer to obtain substrates with a cured film for evaluating shear strength (adhesive strength) according to Examples 1 to 15 and Comparative Examples 1 to 5.
[0391] (Evaluation method) The shear strength (adhesive strength) of the 2 mm x 2 mm glass substrate "#1737" bonded to the obtained substrate with the cured resin film was measured using a die shear tester (manufactured by Arctec Corporation). A grade of △ or higher was deemed to be acceptable.
[0392] (Evaluation Criteria) ◎: Shear strength (adhesive strength) is 20 MPa or more ○: Shear strength (adhesive strength) is 18 MPa or more and less than 20 MPa △: Shear strength (adhesive strength) is 16 MPa or more and less than 18 MPa ×: Shear strength (adhesive strength) is less than 16 MPa
[0393] The evaluation results are shown in Tables 3 and 4.
[0394] [Table 3]
[0395] [Table 4]
[0396] [Reference experiment: Solvent immersion evaluation] As a reference experiment, an alkaline solution immersion evaluation was performed under milder conditions than the above alkaline resistance evaluation. Among the cured films of the substrates with cured films used in the above alkaline resistance evaluation, the substrates with cured films according to Examples 1, 6, 10, and 13 and Comparative Example 5 were immersed in a 5 wt% sodium hydroxide aqueous solution at 25°C for 30 minutes, and then washed and dried. Thereafter, the thickness of the cured film after the test was measured using a stylus-type step shape measuring device "P-17" (manufactured by KLA Tencol Corporation). A grade of △ or higher was considered to be acceptable.
[0397] The remaining film rate in the chemical resistance evaluation was calculated from the following formula, where the film thickness before the test was L1 and the film thickness after the test was L2. Remaining film rate (%)=L2 / L1×100
[0398] (Evaluation Criteria) ○: Residual film rate is 90% or more △: Residual film rate is 80% or more and less than 90% ×: Residual film rate is less than 80%
[0399] The evaluation results are shown in Table 5.
[0400] [Table 5]
[0401] As is clear from Tables 3 and 4, by setting the content of component (B) in the composition for forming an adhesive layer to 25% by mass to 70% by mass relative to the mass of component (A), it was possible to achieve both laser processability (peelability) and alkali resistance, and the shear strength (adhesive strength) was also at an acceptable level.
[0402] As can be seen from a comparison of Examples 1, and 7 to 11, when the component (B) has at least one aromatic ring or alicyclic structure in the molecule, the alkali resistance is improved even when the added amount is the same.
[0403] As can be seen from a comparison of Examples 1, and 7 to 11, it was found that by making the absorbance of component (B) at 266 nm 0.10 or more, the processability (peelability) of the adhesive layer with a 266 nm laser can be improved.
[0404] As can be seen from a comparison of Examples 1, and 12 to 15, by setting the content of component (C) to 1 mass % to 10 mass % relative to the total mass of components (A) and (B), it is possible to improve the shear strength (adhesive strength) while maintaining the laser processability (peelability) and alkali resistance.
[0405] In addition, as can be seen from the reference experiment, even in the comparative example, the alkaline solution immersion evaluation was at an acceptable level under mild alkaline treatment conditions. This shows that the alkaline resistance evaluation of this example was performed under strict evaluation conditions, and that the adhesive layer according to this embodiment has high alkaline resistance. [Industrial Applicability]
[0406] The present invention can provide a laminate having an adhesive that can be used in the manufacture of various products, and in particular, can provide a laminate suitable for a process in which the laminate is temporarily attached to a support such as a semiconductor wafer and processed.
Claims
1. A laminate having an adhesive layer between a light-transmitting support and an adherend, A composition for forming an adhesive layer, which enables the support and the adherend to be separated from the laminate by irradiating light from the support side, The adhesive layer-forming composition is (A) an unsaturated group-containing alkali-soluble resin; (B) an epoxy compound having at least two epoxy groups; (D) a solvent; Including, The content of the epoxy compound (B) is 25% by mass to 70% by mass based on the total mass of the unsaturated group-containing alkali-soluble resin (A). Composition for forming adhesive layer.
2. The epoxy compound (B) has an aromatic ring and / or an alicyclic structure. The adhesive layer-forming composition according to claim 1 .
3. The epoxy compound (B) is The absorbance of a 0.001 wt% acetonitrile solution is measured using an ultraviolet / visible / infrared spectrophotometer in a quartz cell with an optical path length of 1 cm, and the absorbance of light at a wavelength of 266 nm is 0.10 or more. The adhesive layer-forming composition according to claim 1 .
4. The unsaturated group-containing alkali-soluble resin (A) is The weight average molecular weight is 1,000 to 40,000, The acid value is 20 mgKOH / g to 200 mgKOH / g. The adhesive layer-forming composition according to claim 1 .
5. (C) a polymerizable compound having at least one ethylenically unsaturated bond, The content of the polymerizable compound (C) is 1% by mass to 10% by mass based on the total mass of the unsaturated group-containing alkali-soluble resin (A) and the epoxy compound (B). The adhesive layer-forming composition according to claim 1 .
6. A support; An adherend; An adhesive layer comprising a coating film or a cured film of the adhesive layer-forming composition according to any one of claims 1 to 5, which is disposed between the support and the adherend; A laminate having the following structure:
7. a resist layer disposed on a surface of the adherend opposite to a surface on which the adhesive layer is disposed, The resist layer is disposed in contact with an adherend, or disposed so as to sandwich a material layer between the resist layer and the adherend. The laminate according to claim 6.
8. The adhesive layer is provided on a surface of the adherend opposite to the surface on which the adhesive layer is provided. The laminate according to claim 6.
9. A step of forming an adhesive layer on one or both of the surfaces of a support and an adherend using the adhesive layer-forming composition according to any one of claims 1 to 5; a step of adhering the support and the adherend via the formed adhesive layer; A method for producing a laminate comprising the steps of:
10. providing a resist layer on the adherend, The resist layer is disposed on a surface opposite to a surface on which the adhesive layer is disposed. A method for producing the laminate according to claim 9.
11. Providing a laminate according to claim 6; A step of irradiating the adhesive layer with light to separate the support and the adherend; A method for treating a laminate, comprising: The support transmits light having a wavelength of 10 nm to 400 nm. Methods for processing laminates.
12. A support; An adherend; An adhesive layer comprising a coating film or a cured film of the adhesive layer-forming composition according to any one of claims 1 to 5, which is disposed between the support and the adherend; an unexposed resist layer disposed on a surface of the adherend opposite to a surface on which the adhesive layer is disposed; providing a laminate having an exposure step of irradiating a portion of the resist layer with radiation through a photomask; a developing step of developing the resist layer irradiated with radiation and removing the resist layer in exposed or unexposed areas; a stripping step of stripping the resist layer with an alkaline stripping solution; A method for producing a laminate including a patterned material layer, comprising:
Citation Information
Patent Citations
Laminated body and method for separating laminated body
JP2012106486A